Salinity-dependent nitrifier adaptation shapes partial nitritation resilience under dynamic saline conditions: Mechanistic insights into Nitrosomonas salt adaptation - Yunjing Wang; Cong Wang; Xiaoyu Han; Jiayuan Ji; Jian Song; Mingming Zhang; Weikang Qi; Yongzhen Peng (Water Research, 2026)

The role and mechanism of TNFRSF21 in promoting necroptosis of vascular endothelial cells and inducing vascular leakage in sepsis - Juntao Wang; Bindan Zhang; Yujia Wu; Weichao Li; Yuxi Zhang; Daiqin Bao; Haoyu Pei; Caifeng Shi; Han She; Xiaoyan Wang; Qingxiang Mao; Cong Yu (Journal of Molecular Medicine, 2026)

Migration and transformation patterns of pesticides and their transformation products across the groundwater-surface water continuum - Jun Liu; Mengwen Liu; Guiyao Xiong; Yi Cheng; Cong Han; Hao Geng; Xuebing Wang; Si Wei; Nanyang Yu; Xiaobin Zhu; Jianfeng Wu; Xiankui Zeng; et al. (Water Research, 2026)

Palaeoenvironmental evolution and stage-dependent organic matter enrichment in the Late Permian Longtan Formation, Upper Yangtze Block, South China - Hai-Feng Chen; Xin Jin; Marcello Caggiati; Ting-Cong Ren; Bo Luo; Lin-Hao Fang; Hua-Wen Cao; Yang Liu; Chang-Cheng Huang; Bin Xiao; Zi-Han Ma; Hui-Dong Yu; et al. (Sedimentary Geology, 2026)

Mineral–mediated multiple defect g–C3N4 for enhanced peroxide photoactivation: Insights into defect synergy and selective removal of electron–rich pollutants - Jie Wang; Yanbai Shen; Sikai Zhao; Ruixue Ma; Haiyi Lv; Cong Han; Wenbao Liu; Baoyu Cui (Chemical Engineering Journal, 2026)

Novel dual-functional depressant for the selective depression behavior and mechanism of fluorite and calcite in bastnaesite flotation - Ruiqi Ge; Wenbao Liu; Yonglun Wang; Bohan Wang; Wengang Liu; Sikai Zhao; Cong Han; Yanbai Shen (Minerals Engineering, 2026)

Depth-dependent multi-kingdom microbial interactions and biogeochemical cycling genes in eutrophic shallow lake sediments - Yujie Mao; Cong Wang; Lu Zhang; Borui Zou; Maozhen Han; Zhi Wang (Journal of Environmental Sciences, 2026)

Morphological engineering and valence state strategy enable stable nitrate-to-ammonia electroconversion at copper surface in the wide pH range - Yue-Han Qin; Xiao-Hui Wang; Ze-Nong Zhang; Shi-Bin Yin; Cong-Cong Han; Xuan Ai; Shu-Ni Li; Xin Wang; Yu Chen (Chemical Engineering Journal, 2026)

Biobased dynamic vitrimer network enables high intrinsic thermal conductivity, closed-loop recycling and strong adhesion - Hongmin Sun; Xu Han; Dewang Hou; Cong Guo; Ying Wang; Xiahui Jiang; Ruiguang Li; Chengjie Li (Chemical Engineering Journal, 2026)

An all-in-one endoluminal acoustofluidic system enables spatiotemporal transmucosal drug delivery and barrier repair for inflammatory bowel disease - Yichen Liu; Xiaoming Zheng; Yang Qin; Jing Han; Zhiwei Cong; Shu Fan; Yan Li; Ruochen Wang; Xiaolong Guo; Qichao Huang; Xunan Jing; Yibo Liu; et al. (Chemical Engineering Journal, 2026)

SIRT7-mediated H3K79 desuccinylation modulates functional activities of goat ovarian granulosa cells - Yawen Li; Lei Wang; Shuaifei Song; Qiuyan Li; Ying Gong; Zihan Wang; Shiyi Yao; Zihan Ma; Yingping Xia; Cong Zhou; Xinyang Yao; Jia Luo; et al. (Theriogenology, 2026)

Soil nematode response to nitrogen addition correlates with initial abundance - Yang Hu; Mengfei Cong; Yubin Wang; Tianle Kou; Han Yan; Jinshi Jian; Hongtao Jia; Shaoshan An (Soil and Tillage Research, 2026)

The role of transcription factor MdGeBP3 in Modulating cold stress tolerance and anthocyanin biosynthesis in apple - Ming-Kun Wang; Ran-Xin Liu; Cong-Yu Xu; Yue-Ning Wang; Xiao-Han Qin; Shan-Shan Li; Ying-Xue Lv; Du Liu; Jie Lu; Xiao-Fei Wang (Journal of Plant Physiology, 2026)

Wing phenotypic divergence and venation variation: association with ultrasonic courtship song profiling in Ostrinia furnacalis (Lepidoptera: Crambidae) - Xiao Feng; Cong Zhang; Jingyu Wang; Xiao Han; Sohail Abbas; Qiyun Li; Rizhao Chen (Journal of Insect Physiology, 2026)

Global peatlands formed via paludification since the Last Glacial Maximum are more conducive to absorbing CO2 - Yunlong Gao; Jiangtao Gao; Jinxin Cong; Dongxue Han; Guangxin Li; Guoping Wang; Bei Li; Chuanyu Gao (Global and Planetary Change, 2026)

Function identification of nitrogen forms in nitrogen-doped biochar for promoting methane production in anaerobic digestion - Xiao-Yue Cao; Cong-Cong Tang; Shuo-Han Chen; Sheng-Jie Sun; Chun-Xue Yang; Ai-Juan Zhou; Zewei Liu; Zhang-Wei He (Environmental Research, 2026)

Aggregate-specific microbial adaptive strategies to nitrogen addition regulate carbon and nitrogen use efficiencies in a meadow steppe - Zhirui Wang; Tianpeng Li; Changming Lu; Jiangping Cai; Xue Feng; Mikhail V. Semenov; Cong Wang; Xiaotao Lü; Heyong Liu; Osbert Jianxin Sun; Xingguo Han; Irina Kravchenko; et al. (CATENA, 2026)

Spatial and temporal evolution of the groundwater depth and indirect effects during the spring irrigation period in the Hetao Irrigation District - Yi Zhao; Haibin Shi; Xianyue Li; Shuya Yang; Haoqi Han; Yunlei Dong; Qingfeng Miao; Jianwen Yan; Cong Hou; Xu Dou (Irrigation Science, 2026)

Primary amine-functionalized HTO/CMC/PVA composite films: Highly selective lithium adsorption and applications in complex lithium-containing systems - Shengkai Liu; Ruimeng Liu; Wenxuan Wang; Dandan Hu; Yu Han; Cong Li; Huiling Li; Chang Wan; Tai Peng; Wei Wang; Daxin Liang (Process Safety and Environmental Protection, 2026)

Deep learning-based shipborne sea-ice segmentation for ice-channel perception during Arctic convoy operations - Shouwen Li; Jiahui Fu; Lixuan Han; Cong Liu; Mingyang Zhang; Hongdong Wang (Ocean Engineering, 2026)

Exogenous calcium modulates oxalic acid metabolism via repression of LcAAE3 and mediates calcium accumulation in litchi pericarp and fruit pedicel - Dong-Cheng Li; Zhi-Qun Zhong; Teng-Kai Chen; Yi-Tong Liu; Yue-Han Sun; Hui-Cong Wang; Ren-Fang Zeng; Xu-Ming Huang (Journal of Plant Physiology, 2026)

Interactive effects of vegetation and water regimes on evaporative fraction from two coastal wetland ecosystems - Qiong Han; Tiejun Wang; Qinling Bai; Cong-Qiang Liu (Journal of Hydrology, 2026)

Reversible anhydride-alcohol network enables highly thermal conductive phase change composites for thermal management and thermoelectric generator - Dewang Hou; Hongmin Sun; Xu Han; Cong Guo; Ying Wang; Yifan Xue; Ruiguang Li; Chengjie Li (Chemical Engineering Journal, 2026)

2-Methoxyestradiol Suppresses Stemness and Epithelial-Mesenchymal Transition in Drug-Resistant Esophageal Squamous Cell Carcinoma by Targeting the Snail Signaling Pathway in Cancer Stem Cells - Jie Yan; Shuhua Han; Keqi Zhang; Linlin Li; Mingjing He; Haoqing Cao; Meiru Zhu; Bingjie Bi; Qiang Xu; Cong Wang (Stem Cell Reviews and Reports, 2026)

Stable leaf pH of grassland community under nitrogen inputs ensured by contrasting intra- and inter-specific variations - Xiao-Hua Yang; Cong Ding; Xiao-Sa Liang; Yuan-Xiu Wu; Xiao-Ru Zhang; Xiao-Jing Zhang; Liang-Chao Jiang; Xing-Guo Han; Xiao-Tao Lü (Plant and Soil, 2026)

The CMA Chemistry–Weather Coupled Model and Its Operational Forecast of Fog–Haze and Sand/Dust Storms - Hong Wang; Xiaoye Zhang; Wenjie Zhang; Yue Peng; Ping Wang; Hongli Liu; Zhaorong Zhuang; Liping Huang; Weihong Tian; Yang Zhao; Ke Gui; Chen Han; et al. (Journal of Meteorological Research, 2026)

Fish diversity and community turnover across protection zones in multiuse marine protected areas - Xu Zeng; Cong Zeng; Yongfeng Zhou; Yue Liu; Zheying Lin; Jihao Peng; Yihui Jiang; Han Dong; Guodong Li; Shuangzhao Li; Hengyu Li; Ling Cao (Conservation Biology, 2026)
Multiuse marine protected areas (MMPAs) with varying levels of protection in different zones are increasingly being adopted to balance conservation and socioeconomic goals. However, the effect of these zone‐based strategies on fish diversity is not well understood. We used environmental DNA surveys across zones with different protection levels (fully protected, highly protected, and lightly protected) in three typical Chinese MMPAs, while controlling for environmental factors and human activities, to examine fish species composition and richness among zones. Contrary to expectations, sites with high levels of protection had lower fish species richness than sites with lower levels of protection. Turnover in community composition between fully protected and less protected zones was 88.4% and accounted for 96.4% of pairwise dissimilarities. Rather than diminishing the importance of high‐level protection, our results showed that a tiered zoning approach can sustain fish species richness and limit biotic homogenization. Our results challenge the assumption that strict protection universally leads to high species richness and demonstrate that nuanced multilevel protection zoning may be more effective at preserving marine biodiversity and ecosystem functions at broader spatial scales.

Correction: Autogenic and climatic drivers of vegetation succession in a thermokarst lake-margin peatland, northern Greater Khingan Mountains - Dongxue Han; Jiangtao Gao; Jinxin Cong; Guoping Wang; Chuanyu Gao (Vegetation History and Archaeobotany, 2026)

NPY-Y2R driven neuroimmune signaling as a potential therapeutic target for trigeminal neuralgia: clinical and experimental evidence - Zi-Le He; Chao Xu; Qi-Fan Yang; Cong-Zhou Han; Ting Wu; Yu-Qing Xu; Yun-Ze Liu; Liang-Yu Ni; Si-Qi Jia; Tang-Yu Zhang; Yun Wang; Yi Feng (Science Bulletin, 2026)

Mechanistic insights into glufosinate-ammonium (GLA)-Induced brain injury revealed by LC-MS/MS-based metabolomics - Huan-le Ye; Xin-xin Zheng; Mian-mian Li; Zhi-qiang Zhang; Liu-xu Chen; Wen-jing Zhang; Ren Cheng-Han Fan; Guo-xin He; An-cong Xu (Chemico-Biological Interactions, 2026)

Influence of inundation frequency on soil organic carbon stability in northern China's estuarine wetlands - Zhanhang Liu; Hu Ding; Xiaokun Han; Hao Xue; Chunmei Chen; Cong-qiang Liu; Yunchao Lang (Applied Geochemistry, 2026)

Evaluating the quality and reliability of DILI in Chinese videos on TikTok (Douyin) and BiliBili: cross-sectional content analysis study - Ruogu Nie; Bing Yu; Han Wang; Shengying Qin; Cong Huai; Zhiling Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Conversion of polyethylene to monoaromatics via a tandem catalytic strategy - Zhiye Ma; Ziyu Cen; Tianrui Bi; Weilong Wen; Cong Luo; Zhijuan Zhao; Baolong Qu; Xiaoyu Zhang; Qinglei Meng; Huizhen Liu; Longfei Lin; Buxing Han (Science Bulletin, 2026)

Thermo-mechanical upcycling of waste rubber-polyethylene into asphalt: Performance optimization and GHG mitigation - Yuzhao Han; Hui Li; Saad Khan; John Harvey; Angel Mateos; Cong Ma; Lei Wang (Resources, Conservation and Recycling, 2026)

Enhancing CO2 capture performance of K2CO3 derived from KHCO3 precursor via dispersion on non-porous SiO2 - Ziqiang Han; Cong Luo; Xiaoshan Li; Zhen Du; Zewu Zhang; Fan Wu; Liqi Zhang (Journal of Environmental Chemical Engineering, 2026)

Carbon footprint analysis and its underlying drivers in a mega-urban region: Evidence from the Beijing–Tianjin–Hebei urban agglomeration - Ke Yang; Rong-Gang Cong; Qi Han; Yifu Ou (Journal of Cleaner Production, 2026)

Heavy-metal and nutrient enrichment triggered a regime shift in marsh diatom assemblages over the past millennium - Dongxue Han; Jinxin Cong; Lin Li; Guoping Wang; Chuanyu Gao (Journal of Environmental Management, 2026)

Two phases of early Palaeozoic magmatism at the Wude area in the western Bainaimiao arc (Inner Mongolia, China): Petrogenesis and tectonic implications - Cong Ding; Zhicheng Zhang; Yunxi Meng; Jianzhou Tang; Qi Wang; Huaihui Zhang; Baofu Han (Acta Geochimica, 2026)

Emerging Viruses in Decapod Crustaceans: A Global Review - Xuan Dong; Guohao Wang; Kejun Wang; Kaisong Zhang; Hua Xu; Liying Wang; Xuan Li; Liang Qiu; Win Surachetpong; Jing Wang; Jee Eun Han; Kathy F. J. Tang; et al. (Reviews in Aquaculture, 2026)
Due to its advantages of a short production cycle, wide market demand, and profitability, decapod crustacean aquaculture has become one of the fastest‐growing food production systems. However, disease outbreaks have become one of the most important factors limiting the sustainability of decapod crustaceans. This review synthesizes current advancements in the understanding of emerging viral pathogens in decapod crustacean aquaculture, with emphasis on their genomic‐based taxonomical classification, susceptible hosts, global distribution, clinical manifestations, pathogenic mechanisms, diagnostic developments, and management strategies. This paper summarizes details of emerging viruses with confirmed pathogenicity (such as decapod iridescent virus 1), as well as viruses with uncertain or yet‐unconfirmed pathogenic roles. In addition, we highlight the role of next‐generation sequencing in virus discovery and examine the challenges posed by coinfection with other microorganisms. This review provides information to help the decapod crustacean aquaculture industry in setting up early warning systems to prevent the introduction of emerging pathogens into the production systems.

Autogenic and climatic drivers of vegetation succession in a thermokarst lake-margin peatland, northern Greater Khingan Mountains - Dongxue Han; Jiangtao Gao; Jinxin Cong; Guoping Wang; Chuanyu Gao (Vegetation History and Archaeobotany, 2026)

Numerical investigation of cavitation and vortex evolution characteristics in a hull-propeller-rudder coupled system - Chao Wang; Yi-Ming Hu; Cong Sun; Yu Zhao; Yang Han; Lian-Zhou Wang; Jia-Xiu Cao (Ocean Engineering, 2026)

Smad7 drives cisplatin resistance in ovarian cancer via a PRMT5-dependent mechanism - Jinlong Ji; Kexin Wang; Geshuyi Chen; Manman Zhao; Cong Wan; Yun Han; Yanli Zheng (Tissue and Cell, 2026)

Effect of the combination of lactic acid, ε-poly-L-lysine and sodium isoascorbate on the swelling, microbiomics variation, and quality attributes of vacuum-packed fresh cut lotus root - Jiahui Jiang; Qianlong Shi; Dan Li; Qingmin Chen; Cong Han; Jing Wei; Maorun Fu; Huaimei Cao; Xiaofei Xin (Postharvest Biology and Technology, 2026)

A cellulosic waste-upcycled 1T/2H-MoS2/biochar heterostructure for efficient cationic dye adsorption via a multi-anchor chemisorption mechanism - Yifan Lu; Min He; Mingna Ge; Luning Chen; Lin Han; Cong Tu; Bang Yuan; Jie Huang (Journal of Environmental Chemical Engineering, 2026)

Reductive pyrolysis of heavy metal Gypsum: Impurity phase evolution and transformation pathways - Xiaobo Min; Zidong Tan; Yunyan Wang; Yun Li; Han Lu; Changhao He; Yong Ke; Cong Peng (Journal of Environmental Management, 2026)

Non-negligible risk of nitrogenous disinfection byproducts arising from the chlorination of ammonia-containing source water - Guangrong Sun; Dongquan Li; Feiyang Huang; Han Yeong Kaw; Hainan Wu; Haibing Cong (Journal of Environmental Chemical Engineering, 2026)

From digestion to delivery: the gastrointestinal fate and functional duality of goat milk-derived extracellular vesicles - Chunping Chen; Cong Zheng; Fangcheng Hu; Yue Li; Xingyuan Liu; Wenxu Zhou; Baolong Liu; Lin Han; Caian He; Min Wang (Food Chemistry, 2026)

A Deep-Learning Model for Stroke Subtype Identification in Moyamoya Disease Based on Digital Subtraction Angiography - Zhi-wen Liu; Fei Shang; Ri-Miao Yang; Cong Han; Shuai Liu; Guo-zheng Xu (Translational Stroke Research, 2026)

SPARC: A programmable molecular diagnostic platform based on a signal-triggered, self-supplied crRNA and tiered PER-transcription-CRISPR cascade for early detection of hepatocellular carcinoma - Xinying Chang; Cong Han; Haishuo Ji; Zhe Zeng; Jingyi Yang; Qirui Liu; Chao Jia; Lili Zhao; Chunlei Zhou; Shujia Chen; Wolfgang Knoll; Jia Li; et al. (Analytica Chimica Acta, 2026)

Microbial metabolism decline in degraded grasslands depends on soil organism size - Yang Hu; Mengfei Cong; Tianle Kou; Han Yan; Xinya Sun; Haolin Zhang; Yakov Kuzyakov; Yang Yang; Yimei Huang; Yanxing Dou; Zhaolong Zhu; Baorong Wang; et al. (Agriculture, Ecosystems & Environment, 2026)

Emerging contaminants disrupt the nitrogen cycle in coastal hydrological systems: Insights from synergistic effects of weakly-correlated emerging contaminants - Guiyao Xiong; Mengwen Liu; Xiaobin Zhu; Hao Geng; Cong Han; Yi Cheng; Yun Yang; Guangquan Chen; Xingyong Xu; Jianfeng Wu; Jinguo Wang; Nanyang Yu; et al. (Water Research, 2026)

DBH-YOLO: A novel algorithm for surface defects detection of postharvest blue honeysuckle berry fruit - Liangliang Xue; Hongyue Cong; Di Xu; Jingxin Han; Haoran Wang; Chenghai Liu; Xianzhe Zheng (Postharvest Biology and Technology, 2026)

MdHMGB15 enhances zinc tolerance by activating multiple metal homeostasis genes in apple - Ran-Xin Liu; Ming-kun Wang; Yue-Ning Wang; Xiao-Han Qin; Ying-Xue Lv; Shan-Shan Li; Du Liu; Cong-Yu Xu; Xiao-Fei Wang (Journal of Hazardous Materials, 2026)

Stable oleogel system for improved delivery of poorly soluble quercetin - Shengnan Zhang; Lihua Jin; Lu Gao; Han Zhang; Xiaodan Qi; Cong Li; Bang Chen; Yehua Shen (Journal of Food Engineering, 2026)

Hetero-folded hBN/graphene with ultrahigh thermal conduction and electrical insulation for reliable thermal management - Han Zhao; Pengyu Zhang; Jingran Guo; Dizhou Liu; Shixuan Dang; Duola Wang; Hongxuan Yu; Jiali Chen; Chuanyun Song; Yuanpeng Deng; Yingde Zhao; Cong Li; et al. (Chemical Engineering Journal, 2026)

The role of transition metal Y, Ti, and Zr substitutions on the hydrogen storage of Ce2Ni7-type Sm–Mg–Ni-based superlattice alloys - Lian Cong; Zhuohan Zhang; Kuiyue Wang; Yuan Li; Qiuming Peng; Lu Zhang; Shumin Han (Chemical Engineering Journal, 2026)

Wide pH range electrocatalytic nitrate reduction to ammonia over high-performance hollow Cu3P nanocubes - Yong-Qi Zhang; Xiao-Hui Wang; Ying Li; Cong-Cong Han; Xuan Ai; Shu-Ni Li; Yu Chen (Chemical Engineering Journal, 2026)

Flash joule heating-induced synthesis of biowaste-derived metal-free catalysts for nitrate reduction reaction - Xin Chen; Zhaoyu Wang; Liuhong Yang; Runmiao Yuan; Shuyi Huang; Qinyuan Hu; Xue Wang; Cong Gu; Xiangli Wen; Xi Chen; Hongji Zhang; Dongjian Shi; et al. (Bioresource Technology, 2026)

Plant and microbial interactions under different planting patterns regulate nitrogen removal in constructed wetlands - Feng-Cong Jia; Yue Zhang; Yu Han; Xing-Peng Wang; Yu-Hui Yang; Wei-Jie Wang (Bioresource Technology, 2026)

Ultra-high SERS-active nanowires-PTFE composite substrate for trace detection of Aflatoxin B1 in aquaculture water - Liu Wang; Jie Han; Liangyan Sun; Jinru Feng; Xiaohan Lin; Daoliang Li; Cong Wang (Journal of Hazardous Materials, 2026)

Functional analysis of wssv025 gene in the pathogenicity of white spot syndrome virus in Penaeus monodon - Shanel G. Manito; Cong-Yan Chen; Brandon Rafael de Jesús Castillo-Corea; Mary Nia M. Santos; Casiano H. Choresca; Fiona L. Pedroso; Christopher Marlowe Caipang; Han-Ching Wang; Fernand F. Fagutao (Fish & Shellfish Immunology, 2026)

Research on the impact of resident behavior on energy consumption during the heating period of ultra-low energy buildings - Ru-Xi Ding; Jia-Ze Dai; Ying-Nan Zhang; Xiao-Ping Wu; Cong-Han Yu; Zhenfa Fan (Energy and Buildings, 2026)

Assessment of regional damming probability caused by post-earthquake rainfall-induced cascading hazards - Cong Dai; Shuai Zhang; Yingyue Han; Limin Zhang; Te Xiao (Engineering Geology, 2026)

Biomimetic knitted fabric with hierarchical gradient for high-efficiency personal thermal–moisture management - Zhijia Dong; Luyi Han; Xing Feng; Honglian Cong; Yousong Xue; Pibo Ma (Chemical Engineering Journal, 2026)

Nanofibrous core/nanoporous sheath structured ultra–flexible ceramic aerogels for thermal superinsulation - Dizhou Liu; Cong Li; Han Zhao; Hongxuan Yu; Jingran Guo; Shixuan Dang; Duola Wang; Chuanyun Song; Yingde Zhao; Zhengli Yan; Yuanpeng Deng; Jiali Chen; et al. (Science Bulletin, 2026)

An 11,000-year vegetation and climate record from a subalpine peatland in the Luoxiao Mountains, subtropical Southeast China - Xin Zhong; Caifeng Cen; Cong Chen; Aiyan Han; Yongjie Tang; Kangyou Huang (Review of Palaeobotany and Palynology, 2026)

Flow separation and effective roughness height in vegetated flow - Feng-Cong Jia; Yu Han; Wei-Jie Wang (Journal of Hydrology, 2026)

A portable microfluidic platform for on-site detection of Aeromonas hydrophila in aquaculture water using multi-enzyme isothermal rapid amplification - Zhuangzhuang Bai; Yanying Zhang; Chen Li; Jie Han; Tonglei Wu; Cong Wang; Yan Zhang; Daoliang Li (Journal of Hazardous Materials, 2026)

Effects of rubber de-crosslinking on the fatigue behavior of crumb rubber modified asphalt considering thermo-oxidative aging conditions - Bingduo Kang; Guanyu Li; Cong Qi; Honggang Zhang; Shanjian Han; Dongliang Kuang; Huaxin Chen; Wei’an Xuan (Fuel, 2026)

Clumped isotopes tracing methane cycle and budget: a review - Xinchu Wang; Cong-Qiang Liu; Jiaxu Han; Jiarui Liu; Timothy Csernica; Naizhong Zhang; Hu Ding; Jonathan Gropp; Jennifer McIntosh; Si-Liang Li; Sheng Xu; Rob M. Ellam (Earth-Science Reviews, 2026)

Synergistic Zn2+/H+ transport realized by proline-induced hydrogen-bond networks in high-performance MnO2 cathode - Kun Li; Han Zhang; Jianxin Wang; Yongxin Liang; Tiefeng Liu; Shengrong Guo; Zheyu Jin; Zhi Zhang; Chenfeng Guo; Bowen Cong; Bo Wang (Chemical Engineering Journal, 2026)

Dual single sites of single metal atom and molecule ligand on TiO₂ atomic-scale step to boost photocatalytic CO2 reduction - Yuxin Liu; Yang Wang; Yibo Feng; Peixin Cui; Kaiwen Wang; Zhouhao Zhu; Xiaoyuan Zhou; Liyong Gan; Shengqi Chu; Guangcai Chang; Ang Li; Xiaodong Han; et al. (Chemical Engineering Journal, 2026)

Mechanistic insight into N-doping-enhanced CO2 adsorption, activation and selectivity regulation in 0D 2D NT@ZIS S-scheme heterostructures - Hanwen Xu; Yu Wei; Shengjie Hao; Meiyu Cong; Zhenze Han; Taolue Liu; Mingxia Guo; Jialuo Li; Jinxuan Liu; Xin Ding; Yan Gao (Chemical Engineering Journal, 2026)

Investigating cis-regulatory elements and gene expression in multiple tomato varieties using interpretable deep learning - Xiang Ji; Cong Wang; He Zhang; Xiuyi Gong; Chunyu Zhu; Yanshen Zhao; Yang Liu; Zhongzhi Han; Hang He (Theoretical and Applied Genetics, 2026)

Targeting P2X7R Protects the Retina Against High-Altitude Hypoxia via NLRP3–Mediated Pyroptosis Suppression - Keke Ge; Yange Gu; Huan Xi; Siyuan Liu; Yatao Wang; Lu Yang; Cong Han; Xingxing Zheng; Hao Wang; Songjian Huang; Wenfang Zhang (Molecular Neurobiology, 2026)

Time-Resolved Oxidative Stress and Apoptosis in Murine Retina under Acute Hypobaric Hypoxia with Parallel Activation of the LIF–JAK–STAT3 Axis - Hao Wang; Qiang Ye; Songjian Huang; Keke Ge; Cong Han; Huan Xi; Junyi Qiao; Jingrong Feng; Peirun Wu; Yuhan Bao; Yi Yang; Wenfang Zhang (Molecular Neurobiology, 2026)

Positive and negative responses of AMF community and diazotrophic community to peanut genetic diversity - Yanyan Yu; Miaomiao Li; Cong Wang; Zhongjie Sun; Xiongde Dong; Shijie Han; Junqiang Zheng (Applied Soil Ecology, 2026)

Analysis of the probability and distribution patterns of local block instability in the surrounding rock of large section tunnels during construction - Shujun Jiao; Guozhang Ding; Cong Fang; Feng Jiang; Jie Zhang; Han Wu; Gang Wang; Peng He; Wen Zheng; Yue Wu; Zhiyong Xiao (Applied Geophysics, 2025)

Research on decoupling and characterization methods of geological elements based on pre-stack seismic data - Cong Ren; Rong-rong Zhao; Ming-yi Li; Jing-jing Zong; Han-peng Cai; Wenhao Li (Applied Geophysics, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Changes in peatland carbon chemical stability affected by peat accumulating in Sanjiang Plain (Northeast China) during the late Holocene - Jinxin Cong; Chao Gong; Dongxue Han; Guoping Wang; Chuanyu Gao (Quaternary Science Reviews, 2025)

Permafrost peatland development at thermokarst lake margins in the northern Greater Khingan Mountains of Northeast China: Rapid areal increase and carbon accumulation since the 1950s - Jiangtao Gao; Jinxin Cong; Guangxin Li; Yingjie Shi; Dongxue Han; Guoping Wang; Chuanyu Gao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Three-dimensional spatial heterogeneity and causality of microbial communities in soil and groundwater systems under long-term BTEX exposure - Cong Han; Mengwen Liu; Xiaobin Zhu; Guiyao Xiong; Jianfeng Wu; Yun Yang; Jichun Wu (Journal of Cleaner Production, 2025)

Single-cell transcriptomic profiling of goat milk somatic cells highlights immune heterogeneity and epithelial cell-related networks - Ren Tao; Cong He; Liu Yaolong; Liu Chengli; Ruan Pengcheng; Wang Zixuan; Long Hao-yuan; Simone Ceccobelli; Hu Pengfei; Zeng Yan; Han Yanguo; Sun Yawang; et al. (Food Bioscience, 2025)

SpecGuard: A food hazardous substance detection application based on deep learning and EncodeBandCompress spectral bands compression method - Yanshen Zhao; Weiming Shi; Runzhe Zhang; Huayu Fu; Cong Wang; Xiang Ji; Zhongzhi Han (Food Control, 2025)

White spot syndrome virus facilitates and relies on shrimp de novo nucleotide synthesis to support viral pathogenesis - Cong-Yan Chen; Der-Yen Lee; Shih-Shun Lin; Chun-Hung Liu; Saengchan Senapin; Pakkakul Sangsuriya; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

WSSV regulates malate-aspartate shuttle during infection - Yen Siong Ng; Fang-Jyun Guo; Kuan-Lun Huang; Cong-Yan Chen; Shu-Wen Cheng; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Electrode interfacial wettability engineering for high-efficiency synthesis of dimethyl sebacate via Kolbe electrolysis - Linchuan Cong; Xinxin Li; Fuyu Han; Yupeng Wu; Kewen Ma; Ciduo Wang; Nan Lin; Haibo Lin (Chemical Engineering Journal, 2025)

Barnacle-inspired robust adhesive strategy integrating with surface topological engineering for durable fire protection of polyurethane foam - Fenglin Wu; Shihu Han; Xiaoping Hu; Cong Deng (Chemical Engineering Journal, 2025)

CO2-mediated SEI engineering via Li2C2O4 pre-lithiation: A dual-functional strategy for high-stability SiOx/Gr anodes - Lifan Wang; Peng Han; Lin Zhang; Cong Zhong; Min Chen; Ruixiang Li; Yiheng Wu; Zhengping Zuo; Xindong Wang; Xuefeng Wang; Chun Zhan; Guicheng Liu (Chemical Engineering Journal, 2025)

Cool/drought triggered rapid expansion of floating peat mat in shallow lake as new hotspot of carbon sink - Jinxin Cong; Shengzhen Ji; Guangxin Li; Chao Gong; Dongxue Han; Guoping Wang; Chuanyu Gao (CATENA, 2025)

Comparative analysis of sexual dimorphism in ultrastructure of sensilla on antennae, frons, and compound eyes of Azpeytia shirakii Hurkmans (Diptera: Syrphidae) - Bin Mao; Yu-Hui Cong; Ming-Hui Wang; Han-Rui Ren; Yun-Li Xiao (Zoomorphology, 2025)

Proto-oncogene DEK binds to pre-mRNAs and regulates the alternative splicing of Hippo signaling genes in HeLa cells - Dongbo Liu; Wei Sun; Jing Han; Cong Wang; Dong Chen; Yunfei Wu; Yongjie Chang; Bin Yang (Molecular Genetics and Genomics, 2025)

Piceatannol improves autoimmune hepatitis by inhibiting the immune activities of T cells and macrophages through binding with c-Jun - Cong Xu; Chenqi Lu; Wu Wang; Zhimin Wang; Yang Qiu; Min Han; Jun Yang; Shanglin Li (Immunologic Research, 2025)

Decreased nematode energy flow triggers soil microbial necromass loss in degraded grasslands - Yang Hu; Mengfei Cong; Tianle Kou; Han Yan; Yuanbin Jia; Xinya Sun; Haolin Zhang; Bicheng Zhang; Yubin Wang; Hongtao Jia; Shaoshan An (Applied Soil Ecology, 2025)

Mechanisms of salt tolerance: insights into photosystem function and carbon metabolism in tomato seedlings - Xuezhen Li; Yongchao Han; Yundan Cong; Longfei Wang; Yujie Shi; Huifang Liu; Huiying Liu (Plant and Soil, 2025)

Unveiling critical drivers of soil salinity prediction accuracy in remote sensing: a global meta-analysis - Zi’ang Cui; Ruiqi Zhang; Wenhui Wang; Zhaoce Peng; Yifan Wu; Ziyue Zhao; Mohan Li; Yutong Cong; Shaoyan Zhang; Zhenhai Li; Lijing Han; Jianli Ding (Plant and Soil, 2025)

Harnessing Landscape Genomics to Evaluate Genomic Vulnerability and Future Climate Resilience in an East Asia Perennial - Li Feng; Cong‐Ying Wang; Li‐Pan Zhou; Yi‐Han Wang; Jing Wang; Zheng‐Yuan Wang; Tao Zhou; Xu‐Mei Wang (Molecular Ecology, 2025)
In this era of rapid climate change, understanding the adaptive potential of organisms is imperative for buffering biodiversity loss. Genomic forecasting provides invaluable insights into population vulnerability and adaptive potential under diverse climatic conditions, thereby facilitating management interventions and bolstering shaping species‐specific germplasm conservation strategies. We primarily employed landscape genomics approaches, leveraging single‐nucleotide polymorphisms obtained through whole‐genome resequencing of 201 individuals across 43 Rheum palmatum complex populations, to pinpoint adaptive variation and its significance in the context of future climates, delineate seed zones, and establish guidelines for ex situ germplasm conservation. The species complex exhibited strong signatures of local adaptation and differential genomic vulnerabilities across its distribution range, with eastern lineage populations facing significant maladaptation risks under future climate scenarios. Using diverse datasets of putatively adaptive loci and climate change scenarios, we delineated three distinct seed zones within the species' range, estimated varying sample sizes per zone to capture most adaptive diversity, and predicted shifts in seed zone centroids ranging from 48.3 to 359.3 km from historical distributions to mitigate climate change impacts. Collectively, our findings underscore the importance of integrating genomic and environmental data to forecast the adaptive trajectory of an East Asian perennial under anticipated climate changes, guide seed zone delineation for germplasm conservation and enhance population resilience. These results provide a blueprint for designing targeted conservation strategies and restoration plans in other imperilled species.

Novel arneomas A-B and other naphthoquinone active components in Arnebia euchroma I. M. Johnst - Li-Li Han; Yibanuer Reheman; Reyilanmu Maisaidi; Cong-Zhao Fan; Lei-Ling Shi; Sheng-Jie Jia (Natural Product Research, 2025)

Structures and antitumor activities of Arnegutones A–C: A study of three novel active components extracted from Arnebia euchroma - Li-Li Han; Guang-Jie Pan; Si-Qi Li; Yibanuer Reheman; Cong-Zhao Fan; Lei-Ling Shi; Sheng-Jie Jia (Phytochemistry Letters, 2025)

Flow structure and spectral characteristics in regions with highly flexible vegetation - Feng-Cong Jia; Yu Han; Wei-Jie Wang; Jin-Jin Li; Zhen Zhao; Jia-Yu Du (Journal of Hydrology, 2025)

Enhanced compatibilization of waste commingled plastics for high-quality cultivation substrate fabrication through biodegradable ingredients modulation - Shi-Lei Han; Cong-Cong Zhang; Ziyang Liu; Fu-Shen Zhang; Xiao Wang (Journal of Environmental Chemical Engineering, 2025)

Dry cleaning of food-grade plastics on a gas-solid biphase fluidized bed: Efficiency, assessment and mechanism - Ziyang Liu; Cong-Cong Zhang; Fu-Shen Zhang; Shi-Lei Han; Dai-En Yang (Journal of Environmental Chemical Engineering, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Historical effects of organic matter sources and fire intensity on permafrost peatland carbon dynamic in northern Great Khingan Mountains (China) over the last millennium - Jinxin Cong; Guangxin Li; Dongxue Han; Guoping Wang; Chuanyu Gao (Global and Planetary Change, 2025)

Quantum effect modulates the Bi-Ov active sites of S-scheme heterojunction for efficient CO2 photoreduction to CH4 - Hanwen Xu; Shengjie Hao; Meiyu Cong; Zhenze Han; Taolue Liu; Jialuo Li; Yu Wei; Mingxia Guo; Xin Ding; Jinxuan Liu; Yan Gao (Chemical Engineering Journal, 2025)

Characterizing Gray matter atrophy patterns associated with accelerometer-measured sedentary behavior: a population-based study - Minle Tian; Xiaolei Han; Ming Mao; Xiaomeng Li; Yi Dong; Jiahao Ding; Qinghua Zhang; Shi Tang; Xiaojuan Han; Lin Song; Tingting Hou; Lin Cong; et al. (Brain Imaging and Behavior, 2025)
Evidence has linked self-reported sedentary behaviors with dementia and cognitive impairment; however, the underlying mechanisms remain poorly understood. We investigated the associations of accelerometer-measured sedentary behavior patterns with gray matter atrophy patterns in rural-dwelling older adults, while taking into account the manner in which sedentary time is accrued (in short or long bouts). This community-based study involved 911 dementia-free older adults (age ≥ 60 years, 59% women) who participated in both ActiGraph and brain MRI substudies within MIND-China (2018–2020). Sedentary behavior parameters (total sedentary time, mean sedentary bout duration, and sedentary breaks) were recorded with accelerometers. Regional gray matter volumes (GMV) were measured using voxel-based morphometry (VBM) methods. Data were analyzed using the general linear regression models, restricted cubic spline curves, and VBM analysis. There was an inverted U-shaped association between daily sedentary time and GMV in temporal, cingulate, and medial temporal cortex, while longer mean sedentary bout duration was linearly related to decreased GMV in total, frontal, temporal, insula, cingulate, and medial temporal cortex. Greater daily time spent in light or moderate-to-vigorous physical activity (LPA and MVPA) was correlated with larger insula GMV. The VBM analysis suggested that prolonged daily total sedentary time and mean sedentary bout duration were significantly associated with smaller GMV in extensive brain regions, especially in thalamus and insula. In conclusion, gray matter atrophy associated with sedentary behavior in older adults is characterized by reduced GMV in global, frontal, temporal, medial temporal, and cingulate cortex, especially in the insula and thalamus regions.

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Saleucanes A-J, structurally diverse neo-clerodane diterpenoids from Salvia leucantha with anti-neuroinflammatory activity via TLR4/MYD88/NF-κB pathway - Fen-Cong Pan; Han-Fei Liu; Xiao-Die Shu; Xiao-Qiao Yang; Hua-Yong Lou; Wei-Dong Pan; Ni Zhang; Jin-Yu Li (Phytochemistry, 2025)

Efficient sweet potato quality detection using pruned attention-based deep learning - Huayu Fu; Guosheng Xin; Yanshen Zhao; Cong Wang; Zhongzhi Han (Journal of Stored Products Research, 2025)

Revisiting the quantitative relationship between groundwater evapotranspiration and water table depth: A numerical study - Shu-Cong Tan; Xiao-Wei Jiang; Zhi-Yuan Zhang; Peng-Fei Han; Xu-Sheng Wang; Li Wan; Yi-Jian Zeng (Journal of Hydrology, 2025)

The nitrate dynamics affected by land use and saltwater intrusion in the coastal hydrologic interaction systems - Hao Geng; Guiyao Xiong; Mengwen Liu; Cong Han; Yi Cheng; Jichun Wu; Shaohua Cao; Xiaobin Zhu (Journal of Hazardous Materials, 2025)

Novel nanoceria in situ-derived porphyrin heterostructure enhanced electrochemiluminescent and colorimetric dual-mode detection of tetracycline residue in foods - Xueran Shi; Yingbo Cao; Lin Cong; Tiance Gu; Jing Wang; Qian Han (Food Chemistry, 2025)

Boosting nitrogen activation in tin oxides via heteroatom doping for efficient ammonia electrosynthesis - Meiyu Cong; Mingzhu Li; Taolue Liu; Shengjie Hao; Zhenze Han; Hanwen Xu; Mingxia Guo; Xin Ding; Yan Gao (Chemical Engineering Journal, 2025)

Flow paths control on spatiotemporal weathering dynamics in high-relief regions, eastern Qinghai-Tibet Plateau: Insight from dissolved Li-Sr-O isotopes - Tingting Ma; Jun Zhong; Si-Liang Li; Sen Xu; Han Luo; Cong-Qiang Liu (Chemical Geology, 2025)

Aflatoxin detection in naturally contaminated peanuts based on vision transformer and multi-scale convolutional fusion - Cong Wang; Yifan Zhao; Hongfei Zhu; Weiming Shi; Qiong Wu; Huayu Fu; Zhongzhi Han (Food Chemistry, 2025)

Accelerating enrichment of ARGs and MGEs with increasing ammonium removal during partial nitrification treating high-strength ammonia wastewater - Heng Yu; Weiyi Jia; Yuqiu Luo; Rong Zhang; Junkai Zhao; Cong Lu; Yue Dong; Shuo han; Bing Li; Chengtun Qu (Environmental Research, 2025)

TdCCA with Dual-Modal Signal Fusion: Degenerated Occipital and Frontal Connectivity of Adult Moyamoya Disease for Early Identification - Yuchen Ran; Yingwei Fan; Shuang Wu; Chao Chen; Yangxi Li; Tianxin Gao; Houdi Zhang; Cong Han; Xiaoying Tang (Translational Stroke Research, 2025)

Structural characteristics and immunomodulatory activity of an exopolysaccharide from Antarctic Pseudoalteromonas sp. LP6-12-2 - Dezhi Wang; Han Li; Yu Zhao; Bailin Cong; Pengying Zhang (Extremophiles, 2025)

Luteolin-7-O-glucuronide alleviates doxorubicin-induced cardiotoxicity by inhibiting PPAR-mediated ferroptosis - Lishuang Cui; Qing Xia; Yongcheng Wang; Cong Han; Xiaohan Zang; Lijuan Zhang; Jianguo Xing; Ruifang Zheng; Yun Zhang (Toxicology and Applied Pharmacology, 2025)

Timing and structure of the short-lived Dansgaard-Oeschger 6 event in the Asian monsoon system - Qiyue Li; Jingjing Lu; Chenyang Zhang; Guhan Liu; Bin Zhao; Jiaqi Cong; Yue Yang; Kan Zhao; Jinguo Dong; Hai Cheng; Yujie Han; Yijia Liang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Effect of epsilon-poly-L-lysine treatment on swelling, microbial growth and physicochemical quality of vacuum-packed lotus root - Qianlong Shi; Yixuan Wang; Cong Han; Xingfeng Guo; Maorun Fu; Subo Tian; Xiaofei Xin (Food Control, 2025)

Bacteria in the Phylum Bacillota Degrade Nicotine Through the Variant of Pyridine and Pyrrolidine Pathway - Xiu-Ming Liu; Xuan Hai; Cong-Jian Li; Yu-Fan Han; Xing Chen; Yu-Jin Fan; Jian Wu; En-Min Zhou; Yuan-Dong Li; Ling-Ling Yang; Yan-Qing Duan; Xiao-Yang Zhi (Current Microbiology, 2025)

Mechanistic insights into effects of the electronic configurations and crystal structures of iron sulfides on the two-stage Fenton degradation for benzene - Cong Liang; Lei Yang; Jing Li; Lu Han; Yudong Feng; Mengfang Chen; Hangyu Li; Zhen Ni; Zhenyu Kang; Hongtao Sheng; Linbo Qian (Chemical Engineering Journal, 2025)

Enhanced hydrological disturbance and atmospheric pollution on an ombrotrophic peatland (Greater Khingan Mountains, Northeast China) since 1950s inferred from diatom records - Dongxue Han; Yang Sun; Jinxin Cong; Guoping Wang; Chuanyu Gao (Anthropocene, 2025)

Associations between long-term exposure to ultrafine particles and type 2 diabetes: A large-scale, multicenter study in China - Tingting Yang; Yi Guo; Renhua Zhang; Jianqin Zhong; Zixuan Xu; Leilei Liu; Ziwei Peng; Fuchao Wang; Yixuan Jiang; Yixiang Zhu; Qiaolan Liu; Yunyun Wu; et al. (Journal of Hazardous Materials, 2025)

Exergoeconomic analysis and machine learning-based optimization for a near-zero CO2 emission multi-generation system with freshwater production - Wenxing Liang; Yanxia Sun; Cong Han; Jinwen Yang; Fanhua Rong; Jitian Han (Desalination, 2025)

Core-shell structured magnetic beads based on sodium alginate/chitosan for nitrogen removal enhancement - Han Zhang; Bolin Li; Cong Ding; Rui Ni; Xiangyu Lin (Chemical Engineering Journal, 2025)

Low-severity fire promote carbon emissions in permafrost peatlands of the Great Khingan Mountains, Northeast China - Guangxin Li; Long Sun; Shengzhen Ji; Xiao Li; Jinxin Cong; Dongxue Han; Guoping Wang; Chuanyu Gao (CATENA, 2025)

Modeling growth curves to estimate the suitable slaughter age for the ostriches (Struthio camelus) - Ha Xuan Bo; Han Quang Hanh; Do Thi Hue; Dang Vu Hoa; Nguyen Thi Hoa; Nguyen Thanh Cong; Nguyen Thi Vinh; Dang Thuy Nhung; Do Duc Luc (Tropical Animal Health and Production, 2025)
Using an accurate growth curve to estimate the suitable age for slaughter has many benefits for ostrich farming. This study was carried out to compare eight growth curve models for estimating body weight and monthly gain of ostriches raised in tropical conditions and then suggested the suitable slaughter age for these ostriches. Two hundred eighty-two ostriches (124 males and 158 females) were raised from birth to 12 months of age to measure individual monthly body weight, and the growth data was analyzed by R software. Eight growth functions (von Bertalanffy, Bridges, Janoschek, Gompertz, Logistic, Lopez, Richards, and Weibull) were used to create the growth curves of ostrich. The Weibull function was the best model among 8 tested models to describe the growth of both male and female ostriches, and the monthly gain (MG) reached the maximum at the 6 th month of age. The maximum average monthly gain (AMG) was obtained between the 9 th and 10 th month of age for both males and females. The best-fit model in this study (Weibull function) suggests the suitable slaughter ages were estimated from the 9 th to 10 th month of age for both male and female ostriches, with estimated body weights of 93 kg for male and 90 kg for female.

Anti-ferroptosis effects of undescribed abietane diterpenoids from Prunella vulgaris subsp . hispida (Benth.) Hultén - Heng-Li Yan; Xiao-Qiao Yang; Han-Fei Liu; Fen-Cong Pan; Jin-Yu Li; Wei-Dong Pan; Ni Zhang; Hua-Yong Lou; Chao Sun (Natural Product Research, 2025)

Estimating soil cadmium concentration using multi-source UAV imagery and machine learning techniques - Yingyue Han; Shuai Zhang; Cong Dai; Jingyu Peng; Yanbo Chen; Han Ke (Environmental Monitoring and Assessment, 2025)

Zoning effects on fish populations in a key Chinese multi-use marine protected area - Xu Zeng; Yue Liu; Shouyu Zhang; Cong Zeng; Dongyan Han; Kisei R. Tanaka; Mackenzie D. Mazur; Ling Cao (Ocean & Coastal Management, 2025)

Interfacial electron transfer promoted greigite Fenton oxidation of benzene by tungsten disulfide: Enhanced regeneration of dissolved and surface-bounded ferrous iron via W/S-mediated electron donor-shuttle mechanism - Cong Liang; Lei Yang; Jing Li; Lu Han; Yudong Feng; Mengfang Chen; Hangyu Li; Zhen Ni; Zhenyu Kang; Hongtao Sheng; Linbo Qian (Journal of Environmental Chemical Engineering, 2025)

Adaptive Discrepancy Masked Distillation for remote sensing object detection - Cong Li; Gong Cheng; Junwei Han (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Hysteresis elongation behavior of RC beams failing in different modes: Experimental investigation and numerical modelling using smeared crack approach - Zi-Nan Wu; You Dong; Xiao-Lei Han; Jing Ji; Jing-Cong Lin (Engineering Structures, 2025)

Few-layer molybdenite-derived MoS2 nanosheets and SnO2 nanostructures heterojunctions for high-performance NH3 detection: Insights from experimental and DFT analysis - Jinzhou Bai; Chao Tang; Sikai Zhao; Siyao Liu; Wenxin Wang; Cong Han; Qiang Zhao; Yanbai Shen (Chemical Engineering Journal, 2025)

Constraining sulfate sources and its implications on atmospheric pCO2 in Arid Regions: Evidence from the Tarim Basin - Guo-Dong Jia; Jun Zhong; Si-Liang Li; Sen Xu; Han Luo; Cong-Qiang Liu (Chemical Geology, 2025)

Nomogram for Predicting Long-term Outcomes of Encephaloduroarteriosynangiosis in Toddlers with Moyamoya Disease: a Longitudinal and Cross-sectional Study - Qingbao Guo; Yan-Na Fan; Qian-Nan Wang; Jingjie Li; Cong Han; Zhengxing Zou; Simeng Liu; Xiaopeng Wang; Dan Yu; Fangbin Hao; Gan Gao; Qian Zhang; et al. (Translational Stroke Research, 2025)

Embedding cobalt nanoparticles into atomically dispersed cobalt-nitrogen-biochar to promote high-valent cobalt-oxo generation in peracetic acid activation for organics oxidation and mechanism - Taizhuo Ma; Min Wang; Yanbai Shen; Jiadian Wang; Cong Han; Jing Kang (Chemical Engineering Journal, 2025)

Enhanced regeneration of large segmental bone defects via hierarchically structured bioactive scaffolds - Mo-Han Wang; Shao-Meng Wen; Yun-Hong Cong; Huai-Ling Gao; Xian-Yu Zheng; Zi-Xiang Han; Run Wang; Rui Xu; Lu Yang; Wen-Jing Li; Zhao Pan; Jia-Cai He; et al. (Chemical Engineering Journal, 2025)

Three-Dimensional Lattice Modeling of Interaction Behavior Between Hydraulic Fractures and Natural Fractures with Varied Morphologies in Hot Dry Rock - Song Wang; Luqing Zhang; Lin Cong; Jian Zhou; Duoxing Yang; Xiufeng Zhang; Zhenhua Han (Rock Mechanics and Rock Engineering, 2025)

A novel microfluidic colorimetric biosensor for rapid and automatic detection Escherichia coli O157:H7 in aquaponics water - Zhuangzhuang Bai; Bingxiong Wang; Tingyao Gao; Xianbao Xu; Zhuangzhuang Du; Jie Han; Yang Hu; Yu Bai; Liu Wang; Cong Wang; Daoliang Li (Computers and Electronics in Agriculture, 2025)

Fe2+ inhibits spring viraemia of carp virus proliferation via ATG14-dependent autophagy - Zhuo-Cong Li; Can Zhang; Na Xu; Xiao Xu; Ke-Jia Han; Chu-Jing Zhou; Yang-Yang Wang; Bao-Jie Cui; Dan-Dan Chen; Long-Feng Lu; Shun Li (Aquaculture, 2025)

A novel cross-priming amplification technique combined with lateral flow strips for rapid and visual detection of zoonotic Toxoplasma gondii - Yao Liang; Yuan-Hui He; Shu-Feng Yang; Shi-Chen Xie; Yi-Han Lv; Wei Cong; Hany M. Elsheikha; Xing-Quan Zhu (Veterinary Parasitology, 2025)

Grassland degradation-induced soil organic carbon loss associated with micro-food web simplification - Yang Hu; Tianle Kou; Mengfei Cong; Yuanbin Jia; Han Yan; Xingyun Huang; Zailei Yang; Shaoshan An; Hongtao Jia (Soil Biology and Biochemistry, 2025)

Prescribed burning effects on carbon and nutrient cycling processes in peatlands of Greater Khingan Mountains, Northeast China - Shengzhen Ji; Guangxin Li; Jinxin Cong; Huifeng Xu; Dongxue Han; Chuanyu Gao (Science of The Total Environment, 2025)

A nationwide probabilistic risk assessment and a new insight into source-specific risk apportionment of antibiotics in eight typical river basins in China: Human health risk and ecological risk - Cong Men; Haoquan Jiang; Yuting Ma; Hengjiang Cai; Han Fu; Zifu Li (Journal of Hazardous Materials, 2025)

Unraveling carbon mineralization patterns and mechanisms in conservation agriculture: A global synthesis and multi-point experiment - Cong He; Jin-Sai Chen; Shou-Wei Han; Wen-Sheng Liu; Wen-Xuan Liu; Olatunde Pelumi Oladele; Yash Pal Dang; Rattan Lal; Xin Zhao; Hai-Lin Zhang (Journal of Cleaner Production, 2025)

Experimental analysis on breaching mechanism of earth-rock dam induced by landslide generated waves - Zhen-han Du; Jia-Wen Zhou; Shi-Chen Zhang; Qi-Ming Zhong; Hai-Bo Li; Yu-Xiang Hu; Cong-Jiang Li; Jie-Yuan Zhang (Engineering Geology, 2025)

AQP4- and Kir4.1-Mediated Müller Cell Oedema Is Involved in Retinal Injury Induced By Hypobaric Hypoxia - Cong Han; Yuting Li; Xingxing Zheng; Xiaoxia Zhang; Guonian Li; Liangtao Zhao; Zhaoqian Chen; Yi Yang; Wenfang Zhang (Molecular Neurobiology, 2025)

Compatibility of Calycosin-Tanshinone IIA improves Ang II-induced renal artery endothelial cell dysfunction through lncRNA-mRNA co-expression network - YanYun Jiang; Cong Han; WanLi Xu; YuQiu Li; Yao Liu (In Vitro Cellular & Developmental Biology - Animal, 2025)

Enhancing soil ecosystem multifunctionality through combined conservation tillage and legume-based crop rotation in the North China Plain - Wenxuan Liu; Cong He; Shouwei Han; Baijian Lin; Wensheng Liu; Yash Pal Dang; Xin Zhao; Hailin Zhang (Agriculture, Ecosystems & Environment, 2025)

A new isoflavone from the stems of Derris eriocarpa How - Ying Liu; Zhen-Xin Zhu; Yue Lu; Cong Wang; Hong-Cun Liu; Juan Meng; Jin Qi; Xiao-Ning Huang; Xiao-Mei Lu; Wen-Sen Lu; Shu-Han Luo; Hai-Na Liang; et al. (Natural Product Research, 2025)

Cross-shore profile evolution induced by real emergent vegetation in a sandbar-lagoon coast: Laboratory experiments - Cuiping Kuang; Xin Cong; Lixin Gong; Jiantao Liu; Xuejian Han; Wei Xing (Geomorphology, 2025)

A multi-verse optimizer-based CNN-BiLSTM pixel-level detection model for peanut aflatoxins - Cong Wang; Hongfei Zhu; Yifan Zhao; Weiming Shi; Huayu Fu; Yanshen Zhao; Zhongzhi Han (Food Chemistry, 2025)

Spatio-temporal coupling coordination analysis between local governments' environmental performance and listed companies' ESG performance - Xia Wu; Chunxu Hao; Yuhan Li; Chazhong Ge; Xianming Duan; Jing Ren; Cong Han (Environmental Impact Assessment Review, 2025)

Projections of urban land exposure to drought and flood in China - Huiqing Han; Jie Zhao; Ying Cong; Yuanju Jian; Tao Wang (Environmental Monitoring and Assessment, 2024)

Combined treatment of ɛ-polylysine and UV-C inhibited aerobic bacteria growth, and maintained the color, texture, flavor of vacuum-packed fresh-cut lettuce slices - Zhang Xin; Liu Qianqian; Han Cong; Chen Qingmin; Jiao Wenxiao; Fu Maorun (Postharvest Biology and Technology, 2024)

Full-scale performance and microbial community evolution using dopamine modified ceramic membrane submerged membrane biological reactor in treating young landfill leachate - Cong Wang; Hanyang Wu; Runlin Han; Shujun Zhang; Shouqing Ni; Weicheng Li; Weikang Qi; Yongzhen Peng (Journal of Environmental Chemical Engineering, 2024)

Topography alters the optimum timing of peatland initiation across Northeast China during the Holocene - Yakun Chen; Zicheng Yu; Lei Xu; Guoping Wang; Jinxin Cong; Dongxue Han; Chuanyu Gao (Global and Planetary Change, 2024)

2,3-Butanedione inhibited the swelling and microbial growth, maintained flavor and quality attributes of vacuum-packed lotus root - Yixuan Wang; Qianlong Shi; Maorun Fu; Qingmin Chen; Cong Han (Food Control, 2024)

Co-application of phytoremediation with iron-loaded biochar in petroleum and zinc co-contaminated soil - Mengru Zhang; Zhe Liu; Fei Han; Haitao Cong; Weizhi Zhou (Environmental Research, 2024)

Ultrasonic-Microwave extraction of glucoside alkaloids from potato peel residue and its antibacterial activity - Zhongliang Guan; Qingmin Chen; Ye Xu; Cong Han; Min Wang; Tao Zhao; Handong Zhao; Maorun Fu (Natural Product Research, 2024)

Factors Influencing Collateral Circulation Formation After Indirect Revascularization for Moyamoya Disease: a Narrative Review - Gan Gao; Si-meng Liu; Fang-bin Hao; Qian-Nan Wang; Xiao-Peng Wang; Min-jie Wang; Xiang-Yang Bao; Cong Han; Lian Duan (Translational Stroke Research, 2024)

A novel variant (p.A524P) in Spastin is responsible for a Chinese family with hereditary spastic paraplegia - Yu-Han Jin; Yang-Ziyu Xiang; Mei-Fang Zhao; Yi-Hui Liu; Liang-Liang Fan; Xiao-Cong Li (Molecular Biology Reports, 2024)

Identification and culture of functional salivary gland ductal epithelial cells - Han-Shu Zhang; You-Wei Zhao; Xin-Yi Tao; Xin Cong; Li-Ling Wu; Guang-Yan Yu; Yan Zhang (Histochemistry and Cell Biology, 2024)

Non-coding RNA notations, regulations and interactive resources - Mengwei Cheng; Yinhuan Zhu; Han Yu; Linlin Shao; Yiming Zhang; Lanxing Li; Haohong Tu; Luyao Xie; Haoyu Chao; Peijing Zhang; Saige Xin; Cong Feng; et al. (Functional & Integrative Genomics, 2024)

Multilevel metabolic engineering for enhanced synthesis of S-adenosylmethionine by Bacillus amyloliquefaciens - Cong Jiang; Dian Zou; Liying Ruan; Wenyuan Han; Xuetuan Wei (Biotechnology Letters, 2024)

Sulfate availability affect sulfate reduction pathways and methane consumption in freshwater wetland sediments - Hao Xue; Yunchao Lang; Hu Ding; Xiaokun Han; Tiejun Wang; Zhanhang Liu; Wei La; Cong-Qiang Liu (Applied Geochemistry, 2024)

Genome characterization of a novel fowl adenovirus serotype 8b isolate and construction of the reverse genetic system for rapid genome manipulation - Qilong Qiao; Panpan Yang; Junjie Liu; Minghe Xu; Yan Li; Xingyu Li; Mengjia Xiang; Yutao Zhu; Luyao Qiu; Chenghao Han; Dexin Bu; Boshun Zhang; et al. (Veterinary Microbiology, 2024)

Effects of cutting temperature on the genes and fatigue properties of asphalt during its refining process - Guanyu Li; Cong Qi; Shanjian Han; Liang Fan; Dongliang Kuang; Huanxin Chen; Yongchang Wu (Fuel, 2024)

Chemical regulation of lignin spatial conformation for a multifunctional soft material with a novel energy dissipation mechanism - Yingying Su; Xiao Han; Guanda Che; Jinghui Zhou; Yao Li; Sheng Cheng; Cong Wang; Xu Fei (Chemical Engineering Journal, 2024)

Icariin-loaded selenium-gold multi-shell nanocomposites with NIR-II response release to relieve post-damaged bone microenvironment for osteoporosis synergy therapy - Yuqing Li; Xiaotong Feng; Yuwei Li; Qile Song; Naling Long; Xiaoting Fu; Yifan Wang; Yingjiao He; Huiying Yan; Cong Li; Lina Feng; Cundong Fan; et al. (Chemical Engineering Journal, 2024)

Synergistic dielectric and magnetic effects boosting electromagnetic wave absorption in Flower-Ball-like VSe2@CoFe2O4 composites - Jinchang Liu; Leyao Xu; Cong Shao; Zhaolin Liu; Guowei Zhang; Yuang Guan; Yunyao Zhang; Xiaoyi Lei; Yang Dai; Wu Zhao; Junfeng Yan; Han Zhang (Chemical Engineering Journal, 2024)

Effect of black soldier fly larvae frass addition on humus content during low temperature co-composting - Ruju Zhang; Yingpeng Zhang; Yonglan Xi; Jin Zhou; Ting Han; Qiuqin Ma; Cong Wang; Fei Zhu; Xiaomei Ye (Bioresource Technology, 2024)

Bearing Performance of a Helical Pile for Offshore Photovoltaic under Horizontal Cyclic Loading - Xinfu Cong; Zhe Li; Zhonghai An; Jiangxue Liu; Yanqing Han (Journal of Marine Science and Engineering, 2024)
For an offshore photovoltaic helical pile foundation, significant horizontal cyclic loading is imposed by wind and waves. To study a fixed offshore PV helical pile’s horizontal cyclic bearing performance, a numerical model of the helical pile under horizontal cyclic loading was established using an elastic–plastic boundary interface constitutive model of the clay soil. This model was compared with a monopile of the same diameter under similar conditions. The study examined the effects of horizontal cyclic loading amplitude, period, and vertical loads on the horizontal cyclic bearing performance. The results show that under horizontal monotonic loading, the bearing capacities of a helical pile and monopile in a serviceability limit state are quite similar. However, as the amplitude of horizontal cyclic loading increases, soil stiffness deteriorates significantly, leading to greater horizontal displacement accumulation for both types of piles. The helical pile’s bearing capacity under horizontal cyclic loadings is approximately 60% of that under monotonic loading. With shorter cyclic loading periods, horizontal displacement accumulates rapidly in the initial stage and stabilizes over a shorter duration. In contrast, longer cyclic loading periods lead to slower initial displacement accumulation, but the total accumulated displacement at stabilization is greater. When vertical loads are applied, the helical pile exhibits more stable horizontal cyclic bearing performance than the monopile.

Harnessing multimodal data fusion to advance accurate identification of fish feeding intensity - Zhuangzhuang Du; Meng Cui; Xianbao Xu; Zhuangzhuang Bai; Jie Han; Wanchao Li; Jianan Yang; Xiaohang Liu; Cong Wang; Daoliang Li (Biosystems Engineering, 2024)

Whole-genome sequencing of Ganzi horse reveals the genetic diversity and provides unique insights into its plateau adaptation - Jiale Han; Meixuan Lu; Cong Li; Minhao Sun; Qiaoyan Hu; Yidan Li; Halima Jafari; Zhaofei Wang; Pengcheng Zhao; Ruihua Dang (Livestock Science, 2024)

Fabrication of a novel plasmonic Z-scheme AgCl/Ag/CdS photocatalyst for efficient removal of malachite green in seawater: Performance and mechanism exploration - Jize Liu; Wenchao Yang; Cong Gao; Qingqing Jin; Haoxiang Wang; Tianqi Liu; Jianbo Han (Journal of Environmental Chemical Engineering, 2024)

Techno-economic analysis and fuel applicability study of a novel gasifier-SOFC distributed energy system with CO2 capture and freshwater production - Wenxing Liang; Guangdi Liu; Cong Han; Lei Xia; Wanchao Zhu; Jinwen Yang; Jitian Han (Desalination, 2024)

Electrocatalytic formate synthesis from polyethylene terephthalate and carbon dioxide through sulfide-and-reconstruct engineering of catalyst - Shengjie Hao; Meiyu Cong; Zhenze Han; Hanwen Xu; Taolue Liu; Mingxia Guo; Xin Ding; Yan Gao (Chemical Engineering Journal, 2024)

Effects of land reclamation on peatland carbon stability in Sanjiang Plain (Northeast China) over the last century - Jinxin Cong; Guoping Wang; Dongxue Han; Chuanyu Gao (CATENA, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Experimental/numerical investigation on the hydrodynamic and noise characteristics of pump-jet propulsion - Kaiqiang Weng; Cong Sun; Kang Han; Chao Wang; Shuai Sun; Peng Li; Jian Hu (Ocean Engineering, 2024)

Why did the world's largest green tides occur exclusively in the southern Yellow Sea? - Kuishuang Shao; Ning Gong; Lingyu Shen; Xue Han; Zixuan Wang; Kai Zhou; Deyu Kong; Xishan Pan; Pifu Cong (Marine Environmental Research, 2024)

Salinity responsive mechanisms of sulfur-based mixotrophic denitrification and ectoine induced tolerance enhancement - Ran Li; Ya-Nan Hou; Haibo Li; Yi Han; Daohong Zhang; Yuanyuan Song; Cong Huang; Jianbo Guo; Zhihua Liu; Wei Wei; Bing-Jie Ni (Chemical Engineering Journal, 2024)

Alkali-driven Donnan dialysis for efficient ammonia recovery from wastewater: Performance, mechanism and optimization - Zhinan Dai; Yuanyuan Yu; Wenjie Hao; Cong Chen; Maoqin Ao; Jingmei Yao; Chun Yang; Heng Liang; Chuanbo Guo; Le Han (Chemical Engineering Journal, 2024)

Serum deprivation protein response intervenes in the proliferation, motility, and extracellular matrix production in keloid fibroblasts by blocking the amplification of TGF-β1/SMAD signal cascade via ERK1/2 - Peilong Li; Mei Han; Liaoyi Wang; Cong Gao (Toxicology and Applied Pharmacology, 2024)

ε-Polylysine treatment maintains sensory quality, texture, flavor, and inhibits aerobic bacteria growth in vacuum-packed fresh-cut lettuce - Liu Qianqian; Zhang Xin; Han Cong; Chen Qingmin; Sun Fei; Fu Maorun; Zhao Handong; Xiao Zhijian; Tang Zheng (Postharvest Biology and Technology, 2024)

Vegetation factors and atmospheric dryness regulate the dynamics of ecosystem water use efficiency in a temperate semiarid shrubland - Yanmei Mu; Xin Jia; Ziqi Ye; Xulin Guo; Shaorong Hao; Tianshan Zha; Yuqing Zhang; Cong Han; Shengjie Gao; Fei Xing; Shugao Qin; Peng Liu; et al. (Journal of Hydrology, 2024)

Risk Factors for Preoperative Cerebral Infarction in Infants with Moyamoya Disease - Qingbao Guo; Songtao Pei; Qian-Nan Wang; Jingjie Li; Cong Han; Simeng Liu; Xiaopeng Wang; Dan Yu; Fangbin Hao; Gan Gao; Qian Zhang; Zhengxing Zou; et al. (Translational Stroke Research, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

The Role of KDM2A and H3K36me2 Demethylation in Modulating MAPK Signaling During Neurodevelopment - Zongyao Ren; Haiyan Tang; Wendiao Zhang; Minghui Guo; Jingjie Cui; Hua Wang; Bin Xie; Jing Yu; Yonghao Chen; Ming Zhang; Cong Han; Tianyao Chu; et al. (Neuroscience Bulletin, 2024)

Diagnostic performance of mpox virus (MPXV) real-time PCR assays: multicenter assessment and extended sensitivity analysis - Ziqiang Li; Yuqing Chen; Yanxi Han; Zhenli Diao; Tao Huang; Lei Feng; Yu Ma; Cong Liu; Meng Tian; Jing Li; Wanyu Feng; Zihong Zhao; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Ent-eudesmane sesquiterpenoids with anti-neuroinflammatory activity from the marine-derived fungus Eutypella sp. F0219 - Zhong-Ping Jiang; Rui Su; Meng-Ting Chen; Jun-Yi Li; Han-Yu Chen; Lu Yang; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Wan-Shan Li; Yong Rao; Ling Huang (Phytochemistry, 2024)

A polyfunctionalized carbon framework composite for efficient decontamination of Cr(VI) and polycyclic aromatic nitrides from acidic wastewater - Weilong Wu; Han Zhang; Rong Qian; Kunru Yu; Ronghua Li; Kuok Ho Daniel Tang; Xuan Wu; Zhiqiang Guo; Cong Shao; Feixue Yue; Zengqiang Zhang (Environmental Science and Pollution Research, 2024)

Overcoming research challenges: In vitro cultivation of Ameson portunus (Phylum Microsporidia) - Ming Fu; Hongnan Qu; Yongliang Wang; Jingyu Guan; Tian Xia; Kai Zheng; Liyuan Tang; Chunxue Zhou; Huaiyu Zhou; Wei Cong; Jinyong Zhang; Bing Han (Journal of Invertebrate Pathology, 2024)

Pickering extremulsion rich in lipophilic phytochemicals: Preparation, characterization and application - Xu Han; Cong-Jia Duan; Zi-Fei Wei; Jian Xu; Cheng-Dong Nie; Yuan-Hang Chang; Bo-wen Zhai; Yu-Jie Fu (Journal of Food Engineering, 2024)

Mowing aggravates the adverse effects of nitrogen addition on soil acid neutralizing capacity in a meadow steppe - Zhirui Wang; Tianpeng Li; Changming Lu; Cong Wang; Hui Wu; Xinyue Li; Jiangping Cai; Xue Feng; Heyong Liu; Yuge Zhang; Xingguo Han; Hui Li; et al. (Journal of Environmental Management, 2024)

Bimetallic iron-copper nanozyme for determination and degradation of norfloxacin in foods - Cong Cheng; Min Han; Gang Xiang; Xiaoying Fu; Xianxing Wang; Changfang Lu (Food Chemistry, 2024)

Fabrication of smart film based on fish gelatin incorporating phycoerythrin and cellulose nanofibrils to monitor fish freshness - Md Sadek Ali; Truc Cong Ho; Jin-Seok Park; Ji-Min Han; Duraiarasan Surendhiran; Hee-Jeong Lee; Wei Zhang; Byung-Soo Chun (Food Bioscience, 2024)

Two-stage fluidized bed gasification enhanced with oxidative pyrolysis for low-tar producer gas from biomass - Chao Wang; Fangzheng Liu; Lianfeng Zhu; Xinyu Wang; Cong Zhang; Mengjuan Zhang; Zhennan Han; Xin Jia; Guoqing Guan; Xi Zeng; Fang Wang; Guangwen Xu (Fuel, 2024)

Microbial contribution estimated by clumped isotopologues (13CH3D and 12CH2D2) characteristics in a CO2 enhanced coal bed methane reservoir - Xinchu Wang; Biying Chen; Guannan Dong; Naizhong Zhang; Weiyi Liu; Jiaxu Han; Cong-Qiang Liu; Si-Liang Li; John M. Eiler; Sheng Xu (Science of The Total Environment, 2024)

New fossils reveal the Paleogene establishment of relict Craigia (Malvaceae) in its extant range - Jia Li; Shi-Tao Zhang; Xue-Yan Li; Cong-Li Xu; Yuan Zhu; Ruo-Han Zuo; Lin-Bo Jia (Palaeoworld, 2024)

Sulfate radical-assisted photocatalytic degradation of quinoline with WO3/CuFe2O4/Cu Z-scheme system: Comparison of persulfate and sulfite activation - Bihan Sun; Houfen Li; Rong Han; Cong Gao; Rui Li; Aijuan Zhou; Xiuping Yue (Journal of Environmental Chemical Engineering, 2024)

Resistance of biological magnetic ion exchange resin to norfloxacin on the advanced treatment of wastewater - Liqin Han; Cong Shan; Chendong Shuang; Shanshan Xu; Qing Zhou; Rong Ji; Aimin Li; Yang Pan (Chemical Engineering Journal, 2024)

Dry-season length affects the annual ecosystem carbon balance of a temperate semi-arid shrubland - Yanmei Mu; Xin Jia; Ziqi Ye; Tianshan Zha; Xulin Guo; T. Andrew Black; Yuqing Zhang; Shaorong Hao; Cong Han; Shengjie Gao; Shugao Qin; Peng Liu; et al. (Science of The Total Environment, 2024)

Screening of Plant Essential Oils as Potato Sprout Suppressants at Low Storage Temperature - Qingmin Chen; Lixue Yuan; Zhongliang Guan; Fengli Yue; Cong Han; Maorun Fu (Potato Research, 2024)

Proprotein convertase subtilisin/kexin 9 inhibitor downregulates microRNA-130a-3p expression in hepatocytes to alleviates atherosclerosis progression - Jinghan Xu; Junrong Zuo; Chuyi Han; Tingting Li; Dongxia Jin; Fumei Zhao; Hongliang Cong (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Increasing resistance of Tetranychus urticae to common acaricides in China and risk assessment to spiromesifen - Yang Han; Yan-Chao Zhang; Wen-Nan Ye; Shou-Ming Wang; Xin Wang; Cong-Fen Gao (Crop Protection, 2024)

Metal-organic framework-polymer complex-derived single-atomic oxygen reduction catalyst for anion exchange membrane fuel cells - Quoc Hao Nguyen; Vo Dinh Cong Tinh; Sion Oh; Toan Minh Pham; Thach N. Tu; Dukjoon Kim; Jonghee Han; Kyungmin Im; Jinsoo Kim (Chemical Engineering Journal, 2024)

Monoclonal Antibody Targeting CGRP Relieves Cisplatin-Induced Neuropathic Pain by Attenuating Neuroinflammation - Shun Xie; Zhenfang Gao; Jiale Zhang; Cong Xing; Yanxin Dong; Lanyin Wang; Zhiding Wang; Yuxiang Li; Ge Li; Gencheng Han; Taiqian Gong (Neurotoxicity Research, 2024)

Failure analysis and flow dynamic modeling using a new slow-flow functionality: the 2022 Jiaokou (China) tailings dam breach - Chenxu Su; Martin Mergili; Nahyan M. Rana; Shuai Zhang; Cong Dai; Bijiao Wang; Yingyue Han (Landslides, 2024)

Isolation and Cultivation of Carotenoid-Producing Strains from Tidal Flat Sediment and Proposal of Croceibacterium aestuarii sp. nov., a Novel Carotenoid-Producing Species in the Family Erythrobacteraceae - Xiao-Yan Sun; Han Dong; Yu Zhang; Jia-Wei Gao; Peng Zhou; Cong Sun; Lin Xu (Journal of Marine Science and Engineering, 2024)
Carotenoids are extensively used in drugs, cosmetics, nutrients, and foods, owing to their antioxidant and anti-inflammatory characteristics. Diverse marine heterotrophic prokaryotes can accumulate carotenoids and become promising alternatives for the advancement of carotenoids production. In this research, 55 strains were isolated and cultivated from tidal flat sediment in Zhoushan and classified into the phyla Pseudomonadota (n = 24), Bacillota (n = 18), Bacteroidota (n = 9), and Actinomycetota (n = 4). Nine of them accumulated carotenoids, and most of them belonged to the families Flavobacteriaceae (n = 4) and Erythrobacteraceae (n = 4). Among those carotenoid-producing strains, one strain, designated as D39T, was proposed as one novel species belonging to the genus Croceibacterium through polyphasic taxonomy approaches. Genomic annotations and carotenoid compound determinations revealed that strain D39T encoded crtEBIYZG genes and mainly accumulated zeaxanthin as major carotenoids. Furthermore, carotenoid biosynthesis pathway in the majority of Croceibacterium strains were identical with that in the strain D39T, implying that Croceibacterium members can be sources of producing zeaxanthin. This study enhances knowledge of microbial biodiversity in tidal flats, proposes a novel carotenoid-producing Croceibacterium species, and elucidates carotenoid biosynthesis pathway in the genus Croceibacterium, which contribute to enriching marine carotenoid-producing strains and promoting a comprehensive insight into genomic contents of them.

Unraveling the factors influencing CO2 emissions from hydroelectric reservoirs in karst and non-karst regions: A comparative analysis - Wanfa Wang; Si-Liang Li; Jun Zhong; Yuanbi Yi; Fujun Yue; Zenglei Han; Qixin Wu; Ding He; Cong-Qiang Liu (Water Research, 2024)

Selaginellin derivatives from Selaginella tamariscina and evaluation for anti-breast cancer activity - Jing Wen; Dong-Mei Sha; Xiao-Yong He; Yu-Han Tian; Shuai-Cong Ni; Bin He; Yuan Liu; Xin-Jia Yan (Phytochemistry, 2024)

Robust preparation of catalytic PEI@FeOOH fiber membrane for efficient dye degradation - Jin Han; Lilan Huang; Jianyu Wu; Haojie Chen; Jian Pan; Jingqi Han; Feng Ma; Jiao Li; Hailin Cong (Journal of Water Process Engineering, 2024)

Study on the dynamic effects of plateau hypoxic and cold environment on the thermal adaptation of short-term sojourners in Xizang - Guannan Duan; Cong Song; Yanfeng Liu; Zhiguo Fu; Cong Zhang; Xu Han; Yong Li; Yong Zhou (Journal of Thermal Biology, 2024)

Boosting decarboxylation of monomethyl adipate coupling to dimethyl sebacate through Pt electrode at high current density - Linchuan Cong; Yupeng Wu; Nan Lin; Xinxin Li; Fangbing Liu; Fuyu Han; Jin Yang; Ciduo Wang; Haibo Lin (Chemical Engineering Journal, 2024)

m6A modification associated with YTHDF1 is involved in Japanese encephalitis virus infection - Xiao-han Li; Jing Chen; Yu-da Ou; Xiang Zhong; Jia-huan Hu; Rui-cong Sun; Ying-jun Lv; Jian-chao Wei; Yun Young Go; Bin Zhou (Veterinary Microbiology, 2023)

Corrigendum to “Cardamine violifolia as a potential Hg hyperaccumulator and the cellular responses” [Sci. Total Environ., Volume 863(2023), 160940] - Liwei Cui; Xue Tian; Hongxin Xie; Xin Cong; Lihong Cui; Han Wu; Jianxu Wang; Bai Li; Jiating Zhao; Yanshan Cui; Xinbin Feng; Yu-Feng Li (Science of The Total Environment, 2023)

Organic matter sources in permafrost peatlands changed by high-intensity fire during the last 150 years in the northern Great Khingan Mountains, China - Jinxin Cong; Guoping Wang; Dongxue Han; Chuanyu Gao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Effect of ibuprofen (IBU) on the sulfur-based and calcined pyrite-based autotrophic denitrification (SCPAD) systems with two filling modes: Performance and toxic response mechanism - Nengyao Xu; Jianbo Guo; Cong Huang; Haibo Li; Yanan Hou; Yi Han; Yuanyuan Song; Daohong Zhang (Environmental Research, 2023)

Parerythrobacter aestuarii sp. nov., Isolated from Seawater in the Tidal Region of Taizhou - Han Dong; Ren-Zhuang Han; Yu Zhang; Maripat Xamxidin; Peng Zhou; Cong Sun; Wu Qu; Lin Xu (Current Microbiology, 2023)

Extreme precipitation stable isotopic compositions reveal unexpected summer monsoon incursions in the Qilian Mountains - Liangju Zhao; Xiying Dong; Xiaohong Liu; Ninglian Wang; Christopher J. Eastoe; Na Wei; Cong Xie; Hang Liu; Chuntan Han; Ting Hua; Lixin Wang (Science of The Total Environment, 2023)

Characterization of Maribacter polysaccharolyticus sp. nov., Maribacter huludaoensis sp. nov., and Maribacter zhoushanensis sp. nov. and illumination of the distinct adaptative strategies of the genus Maribacter - Jia-Wei Gao; Jun-Jie Ying; Han Dong; Wen-Jia Liu; Dong-Yan He; Lin Xu; Cong Sun (Frontiers in Marine Science, 2023)
Polysaccharides are complex carbohydrates and are abundant in the marine environment. Microbes degrade and utilize them using Carbohydrate-active enzymes (CAZymes), which mediate polysaccharides into the marine carbon cycle. With the continued supply of polysaccharides from the marine environment, tidal flats are also abundant in polysaccharides, resulting in an abundance of marine polysaccharide degrading strains. In this study, three novel strains, designated as D37 T , M208 T , and SA7 T , were isolated from the intertidal sediment samples located in Zhoushan, Zhejiang and Huludao, Liaoning, PR China. The phylogenetic trees using the 16S rRNA gene and genome sequences showed that the three novel strains belonged to the genus Maribacter . The highest 16S rRNA gene sequence similarities between the three novel strains and other strains of the genus Maribacter were 98.7%, 99.2%, and 98.8%, respectively, while the ANI, AAI, and dDDH values between the three strains and the other strains of the genus Maribacter were 70-86%, 67-91%, and 17-30%, respectively, supporting their affiliation as novel species. Combined with other phenotypic and genotypic characterization in this study, three novel species are proposed as Maribacter polysaccharolyticus sp. nov., Maribacter huludaoensis sp. nov., and Maribacter zhoushanensis sp. nov., respectively, for the three strains. Furthermore, we compared all available genomes of Maribacter representatives and found that Maribacter strains could be divided into two groups (A and B). The two groups are different in genome size and G + C content and gene densities of CAZyme, peptidase, and sulfatase. Group A possesses more CAZymes which are related to degrading laminarin, fucoidan, mannan, xylose, and xylan. This result suggests that the two groups may have different niche adaptation strategies. Our study contributes to a better understanding of the role of marine flavobacteria in biogeochemical cycles and niche specialization.

Oxidation and exothermic properties of long flame coal spontaneous combustion under solid-liquid-gas coexistence and its microscopic mechanism analysis - Rongkun Pan; Daimin Hu; Jiangkun Chao; Xuefeng Han; Hailin Jia; Cong Li (Science of The Total Environment, 2023)

Mixed matrix membrane reactor containing core-shell 4A-Fe@Cu Fenton catalyst for high-performance removal of congo red - Lilan Huang; Haimei Chen; Jin Han; Haojie Chen; Jian Pan; Zihan Zhao; Zhichao Dong; Hailin Cong (Journal of Water Process Engineering, 2023)

Contamination characteristics and potential health risk of brominated flame retardants in paddy soils and rice plants around a typical e-waste recycling site in south China - Kailun Luo; Zhihua Qiao; Weiyu Liang; Cong Lu; Mengru Fu; Shanqi Zhou; Yanna Han; Cheng Peng; Wei Zhang (Environmental Pollution, 2023)

NaNO2 additive-assisted Li2O2 decomposition for highly efficient cathode prelithiation of lithium-ion batteries - Rang Xiao; Cong Kang; Yang Ren; Renlong Li; Jiyuan Jian; Binghan Cui; Geping Yin; Xinqun Cheng; Yulin Ma; Hua Huo; Pengjian Zuo; Guokang Han; et al. (Chemical Engineering Journal, 2023)

The heterogeneity of microbial diversity and its drivers in two types of sediments from tidal flats in Beibu Gulf, China - Yong-Lian Ye; Kuo-Jian Ma; Yun-Han Fu; Zhi-Cheng Wu; Ge-Yi Fu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2023)
Mudflats and sandflats are two common types of coastal tidal flats, the structure and function differences of microbial communities between them are still underappreciated. Beibu Gulf is a diurnal tidal regime located in China, the differences between the two type of tidal flats could be more distinct. In this study, we collected a total of 6 samples from Beibu Gulf, consisting of 3 sandflats samples and 3 mudflats samples, classified based on clay and silt content. Generally, the mudflats samples exhibited higher levels of NH 4 + _N and TOC, but lower in ORP and pH. The microbial diversity of the two types of tidal flats was investigated, revealing great differences existed and sandflats had higher microbial richness and diversity than mudflats. Furthermore, we analyzed the association between microbial communities and environmental factors, finding NH 4 + _N to have the highest contribution to the total variation in microbial community structure, and microbial groups such as Desulfobacterota, Campilobacterota, Chloroflexota, Calditrichota, Spirochaetota, Zixibacteria, Latescibacterota and Sva0485 group in mudflats were positively associated with NH 4 + _N. The functions of microbial community were predicted using metagenomic sequences and metagenome assembled genome (MAG). Mudflats contained more genes for carbon fixation. Nitrate and nitrite reduction were widely existed in mudflats and sandflats, but nitrogen fixation was only existed in mudflats, and Campilobacterota , Desulfobacterota and Gammaproteobacteria MAGs were mainly responsible for it. Sandflats composed more genes for ammonium oxidation, but no MAG was found whether in sandflats or mudflats. Microbes in mudflats exhibited a greater abundance of genes related to sulfur cycling, especially in reduction process, unique MAGs in mudflats such as Calditrichota, Chloroflexota, Desulfobacterota and Zixibacteria MAGs are responsible for sulfate and sulfite reduction. Finally, we predicted functions of ammonium related microbes in mudflats based on MAGs and found Campilobacterota and Desulfobacterota MAGs were important for high accumulation of ammonium in mudflats. This study illuminated the structural and functional differences of microbial communities in mudflats and sandflats, providing new insights into the relationship of microbial communities and environment in the tidal flat.

Cytotoxic pyridine alkaloids from a marine-derived fungus Arthrinium arundinis exhibiting apoptosis-inducing activities against small cell lung cancer - Yiwei Hu; Shuai Ma; Xiaoyan Pang; Mengjing Cong; Qianqian Liu; Fanghai Han; Junjian Wang; Weineng Feng; Yonghong Liu; Junfeng Wang (Phytochemistry, 2023)

Diatom evidence for late Holocene environmental change in a permafrost peatland in the northern Greater Khingan Mountains, Northeast China - Dongxue Han; Yang Sun; Zicheng Yu; Ming Jiang; Jinxin Cong; Chuanyu Gao; Guoping Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Copper Azide-based Complexes without Repulsive Steric Clashes between Azides for Advanced Primary Explosives - Yun-Fan Yan; Qian-You Wang; Meng Cui; Hong-Yi Bian; Yong-Fang Han; Jian-Gang Xu; Fa-Kun Zheng; Guo-Cong Guo (Chemical Engineering Journal, 2023)

Experimental study on the morphodynamic evolution of sandbar-lagoon system with emergent vegetation - Xin Cong; Cuiping Kuang; Guangwei Huang; Qingping Zou; Xuejian Han; Chao Shen; Jie Gu (Coastal Engineering, 2023)

Identifying changes in the hydrological connectivity and their drivers in the Liaohe Delta wetland - Kexin Chen; Pifu Cong; Limei Qu; Shuxiu Liang; Zhaochen Sun; Jianbo Han (Ocean & Coastal Management, 2023)

Association between long-term green space exposure and mortality in China: A difference-in-differences analysis of national data in 2000, 2010 and 2019 - Cong-Cong Li; Zhi-Cheng Du; Shu-Jun Fan; Matthew H.E. Mute Browning; Luke D. Knibbs; Michael S. Bloom; Tian-Yu Zhao; Bin Jalaludin; Joachim Heinrich; Xiao-Xuan Liu; Jia-Xin Li; Yi-Dan Zhang; et al. (Science of The Total Environment, 2023)

Strategies for controlling gas evolution reactions to boost the divergent paired electrochemical upgrading of furfural in acidic environment - Xinxin Li; Linchuan Cong; Yupeng Wu; Nan Lin; Fangbing Liu; Deyuan Xin; Fuyu Han; Jin Yang; Weitong Chen; Haibo Lin (Chemical Engineering Journal, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Cloning and functional characterization of MhPSY1 gene from Malus halliana in apple calli and Arabidopsis thaliana - Yuxia Wu; Shuangcheng Wang; Wanxia Wang; Xiu Wang; Yongjuan Dong; Cong Han; Yanxiu Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Genomic and phylotypic properties of three novel marine Bacteroidota from bare tidal flats reveal insights into their potential of polysaccharide metabolism - Kuo-Jian Ma; Yong-Lian Ye; Yun-Han Fu; Ge-Yi Fu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2023)
Special geographical location and abundant organic matter profiles in tidal flats have resulted in great microbial diversity, in which Bacteroidota strains are considered as one of the primary degraders of polysaccharides, playing a crucial role in the carbon cycle. In this study, we collected sediment or sand samples from 34 bare tidal flats in China and investigated the profile of culturable bacteria, selected three Bacteroidota for polyphasic taxonomic analysis and revealed their polysaccharide metabolic potential. Totally, we isolated 352 pure cultured bacteria and they mainly distributed in Bacteroidota , Pseudomonadota , Bacillota , and Actinomycetota . It is shown that the bare tidal flats contained a large number of potential novel species, mainly distributed in Flavobacteriales and Cytophagales within Bacteroidota . Three Bacteroidota strains, M17 T , M82 T , and M415 T , isolated from mudflat were selected for polyphasic taxonomic analysis. The 16S rRNA gene sequence similarity between strain M17 T and Mangrovivirga cuniculi KCTC 72349 T was 99.28%, and less than 90.09% with other species; strain M82 T shared the highest 16S rRNA gene sequence similarity of 97.85% with Pontibacter litorisediminis KCTC 52252 T , and less than 97.43% with other species; strain M415T had higher 16S rRNA gene sequence similarities with type species of genera Eudoraea (92.62-93.68%), Zeaxanthinibacter (92.02-92.91%), and Muriicola (92.21-92.83%). Phylogenetic analysis based on 16S rRNA gene sequences and single-copy orthologous clusters showed that strains M17 T and M82 T represent novel species within the genus Mangrovivirga and Pontibacter , respectively, and strain M415 T represents a novel species of a novel genus within the family Flavobacteriaceae . The potential in polysaccharide metabolism of all these three strains was analyzed by genomes. The analysis revealed that glycoside hydrolases and glycosyltransferases account for more than 70% of the total CAZymes. Additionally, the numbers of polysaccharide utilization loci (PULs) and annotated CAZymes in Cytophagales spp. M17 T and M82 T were found to be higher than those in Flavobacteriales sp. M415 T . Highly specialized saccharolytic systems and the presence of numerous diversified CAZymes for obtaining energy through polysaccharide metabolism were speculated to help the three novel strains adapt to the utilization of both terrestrial and marine polysaccharides.

Quantitative study of in situ chemical oxidation remediation with coupled thermal desorption - Cong Han; Xiaobin Zhu; Guiyao Xiong; Jingxun Gao; Jianfeng Wu; Dong Wang; Jichun Wu (Water Research, 2023)

Effect of boron and nitrogen modulation in metal atoms anchoring on flower-like carbon superstructure for efficient ammonia electrosynthesis - Yanchao Zhao; Shuo Zhang; Cong Han; Qian Lu; Qiuju Fu; Huimin Jiang; Lingzhi Yang; Yanlong Xing; Qiuju Zheng; Jianxing Shen; Liting Yan; Xuebo Zhao (Chemical Engineering Journal, 2023)

Inhibitory effect of ε-poly-L-lysine on fruit Colletotrichum gloeosporioides through regulating organic acid metabolism and exerting membrane-targeted antifungal activity - Jingjing Wu; Jingjing Hu; Wenxiao Jiao; Yamin Du; Cong Han; Qingmin Chen; Xin Chen; Maorun Fu (Postharvest Biology and Technology, 2023)

AI-aided multiscale modeling of physiologically-significant blood clots - Yicong Zhu; Changnian Han; Peng Zhang; Guojing Cong; James R. Kozloski; Chih-Chieh Yang; Leili Zhang; Yuefan Deng (Computer Physics Communications, 2023)

Quantifying the Impact of Hydrological Connectivity on Salt Marsh Vegetation in the Liao River Delta Wetland - Kexin Chen; Limei Qu; Pifu Cong; Shuxiu Liang; Zhaochen Sun; Jianbo Han (Wetlands, 2023)

Field measures of strengthen plant-microbial remediation of PAHs-FQs compound pollution - Lei Zhao; Zhenzhen Han; Mengying Zhou; Cong Lyu; Yu Li (Environmental Science and Pollution Research, 2023)

Investigating food web structure and system function of an artificial reef ecosystem based on carbon and nitrogen stable isotope analysis: implications for reef management - Jie Feng; Xiaolong Zhao; Fan Bi; Wei Zhao; Liang Zhao; Hao Song; Meijie Yang; Zhi Hu; Cong Zhou; Pu Shi; Pengpeng Hu; Peizhen Ma; et al. (Frontiers in Marine Science, 2023)
Introduction Food web is an important basis for identifying trophodynamic processes, and evaluating the structural and functional characteristics of ecosystems. The trophodynamics and system function of artificial reef (AR) ecosystems have rarely been examined. Methods Stable isotope analysis was used to investigate the food web structure and functions of an artificial reef (AR) ecosystem in this study. Results and Discussion The δ13C and δ15N values of particulate organic matter (POM) in AR showed noticeable seasonal changes, and the δ13C value of POM in autumn was significantly higher than that in other seasons (p<0.05). There were no significant seasonal variations in the δ13C values of solid organic matter (SOM), and no significant difference between SOM and POM was observed except in autumn. Moreover, macroalgae did not significantly affect the δ13C values of SOM. Phytoplankton may be the primary nutrient source in the AR ecosystem. The δ13C values of most crustaceans in the AR were approximately between (-17.03 ± 0.22) ‰ – (-17.74 ± 0.07) ‰, higher than those of most fish, indicating that they may have different basal nutrient sources. The trophic level (TL) of invertebrates was between 2.00 and 3.09, and that of fish was between 2.98 and 3.66. The distribution of δ13C and TLs of crustaceans and fish showed that, except for crustaceans, bivalve shellfish and zooplankton might also be important food sources for fish in the AR ecosystem. Conclusion The δ13C and δ15N values of most species in the AR showed good continuity, indicating that they may be mainly produced from the AR ecosystem. Migratory species such as Lateolabrax japonicus and Sepiella maindroni showed higher δ13C values, indicating that they may have migrated from other sea areas. To maintain the stability of the ecosystem structure and function of the AR ecosystem, fishing activities should be carried out following the maximum sustainable yield theory. Future research needs to identify the nutritional relationship between AR and its adjacent sea areas, to depict the food web structure of the AR with higher accuracy.

Porcine Mx proteins inhibit pseudorabies virus replication through interfering with early gene synthesis - Jing Chen; Jia-huan Hu; Rui-cong Sun; Xiao-han Li; Jing Zhou; Bin Zhou (Veterinary Microbiology, 2023)

Differences in the spectral characteristics of dissolved organic matter binding to Cu(II) in wetland soils with moisture gradients - Haifeng Hua; Mingxuan Liu; Cong-Qiang Liu; Yunchao Lang; Hao Xue; Shiyong Li; Wei La; Xiaokun Han; Hu Ding (Science of The Total Environment, 2023)

Role of molecular weight-dependent spectral properties in regulating Cu(II) binding by dissolved organic matter from different sources - Mingxuan Liu; Xiaokun Han; Laodong Guo; Hu Ding; Haifeng Hua; Cong-Qiang Liu; Wei La; Yunchao Lang (Science of The Total Environment, 2023)

Dysregulation of the microbiota-brain axis during long-term exposure to polystyrene nanoplastics in rats and the protective role of dihydrocaffeic acid - Wenbo Jiang; Cong Hu; Yunyan Chen; Yue Li; Xinyi Sun; Huanyu Wu; Ruiming Yang; Yiwei Tang; Fengru Niu; Wei Wei; Changhao Sun; Tianshu Han (Science of The Total Environment, 2023)

Resveratrol-induced SIRT1 activation inhibits glycolysis-fueled angiogenesis under rheumatoid arthritis conditions independent of HIF-1α - Tian-Tian Jiang; Cong-Lan Ji; Li-Jun Yu; Meng-Ke Song; Yan Li; Qiang Liao; Tuo Wei; Opeyemi Joshua Olatunji; Jian Zuo; Jun Han (Inflammation Research, 2023)

Influence of temperature on fouling removal for pipeline based on eco-friendly ultrasonic guided wave technology - Mingkun Huang; Cong Han; Yang An; Zhigang Qu; Chuanxian Chen; Wuliang Yin (Clean Technologies and Environmental Policy, 2023)

Evaluation of the Added Value of Probabilistic Nowcasting Ensemble Forecasts on Regional Ensemble Forecasts - Lu Yang; Cong-Lan Cheng; Yu Xia; Min Chen; Ming-Xuan Chen; Han-Bin Zhang; Xiang-Yu Huang (Advances in Atmospheric Sciences, 2023)

Regulatory role of vitamin A in lipid metabolism and health of Eriocheir sinensis fed different vegetable oil sources - Qincheng Huang; Xiaodan Wang; Zhideng Lin; Jiadai Liu; Han Wang; Cong Zhang; Zhenyu Du; Jianguang Qin; Liqiao Chen (Aquaculture, 2023)

On the extinction depth of freezing-induced groundwater migration - Xiao-Wei Jiang; Hong-Yu Xie; Shemin Ge; Han Tang; Shu-Cong Tan; Xu-Sheng Wang; Li Wan; Yijian Zeng (Journal of Hydrology, 2023)

Cardamine violifolia as a potential Hg hyperaccumulator and the cellular responses - Liwei Cui; Xue Tian; Hongxin Xie; Xin Cong; Lihong Cui; Han Wu; Jianxu Wang; Bai Li; Jiating Zhao; Yanshan Cui; Xinbin Feng; Yu-Feng Li (Science of The Total Environment, 2023)

Biochar as a multifunctional material facilitate the organohalide remediation: A state-of-the-art review - Xueqi Chen; Bin Wu; Wenxin Yang; Guanshu Zhao; Jinglong Han; Cong Huang; Bo Sun; Aijie Wang; Zhiling Li (Chemical Engineering Journal, 2023)

Aerobic glycolysis in colon cancer is repressed by naringin via the HIF1A pathway - Guangtao Pan; Ping Zhang; Aiying Chen; Yu Deng; Zhen Zhang; Han Lu; Aoxun Zhu; Cong Zhou; Yanran Wu; Sen Li (Journal of Zhejiang University-SCIENCE B, 2023)

Landslide displacement prediction based on optimized empirical mode decomposition and deep bidirectional long short-term memory network - Ming-yue Zhang; Yang Han; Ping Yang; Cong-ling Wang (Journal of Mountain Science, 2023)

Fouling-free membrane stripping for ammonia recovery from real biogas slurry - Cong Chen; Zhinan Dai; Yifan Li; Qin Zeng; Yang Yu; Xin Wang; Changyong Zhang; Le Han (Water Research, 2023)

Experiment and evaluation model of liner design for renewal of deteriorated reinforced concrete pipes utilizing cured-in-place-pipe technology - Zhao Yahong; Huang Sheng; Ma Baosong; Zeng Cong; Yan Xuefeng; Ti Zhongsen; Liu Han; Deng Caiying (Tunnelling and Underground Space Technology, 2023)

Sodium para-aminosalicylic acid ameliorates brain neuroinflammation and behavioral deficits in juvenile lead-exposed rats by modulating MAPK signaling pathway and alpha-synuclein - Zhao-cong Li; Yue-song Zhao; Jun-jie Lin; Lei-lei Wang; Han-xiao Song; Cui-liu Gan; Xiao-wei Zheng; Shi-yan Ou; Michael Aschner; Yue-ming Jiang; Jing-jing Luo; Yan Li (Toxicology Letters, 2023)

A novel ternary deep eutectic solvent pretreatment for the efficient separation and conversion of high-quality gutta-percha, value-added lignin and monosaccharide from Eucommia ulmoides seed shells - Cong-Jia Duan; Xu Han; Yuan-Hang Chang; Jian Xu; Gan-Lu Yue; Ying Zhang; Yu-Jie Fu (Bioresource Technology, 2023)

Piceatannol enhances Beclin-1 activity to suppress tumor progression and its combination therapy strategy with everolimus in gastric cancer - Longtao Huangfu; Xiaoyang Wang; Shanshan Tian; Junbing Chen; Xueying Wang; Biao Fan; Qian Yao; Gangjian Wang; Cong Chen; Jing Han; Xiaofang Xing; Jiafu Ji (Science China Life Sciences, 2023)

Assessing historical biomass- and fossil fuel–derived pyrogenic carbon inputs to peatland carbon stocks in the Changbai Mountains (China) - Chuanyu Gao; Jinxin Cong; Dongxue Han; Guoping Wang (Journal of Soils and Sediments, 2023)

Local and Global Abnormalities in Pre-symptomatic Huntington’s Disease Revealed by 7T Resting-state Functional MRI - Juan-Juan Xie; Xiao-Yan Li; Yi Dong; Cong Chen; Bo-Yi Qu; Shuang Wang; Han Xu; Anna Wang Roe; Hsin-Yi Lai; Zhi-Ying Wu (Neuroscience Bulletin, 2023)

Biogas residue biochar still had ecological risks to the ultisol: evidence from soil bacterial communities, organic carbon structures, and mineralization - Ping Cong; Xuebo Zheng; Lanfang Han; Liying Chen; Jintao Zhang; Wenjing Song; Jianxin Dong; Xiaogang Ma (Journal of Soils and Sediments, 2023)

Resin-based iron-manganese binary oxide for phosphate selective removal - Jie Wang; Yongcan Jiang; Musheng Xu; Cong Han; Lichao Zhang; Guanglong Liu (Environmental Science and Pollution Research, 2023)

Ecological distribution of modern diatom in peatlands in the northern Greater Khingan Mountains and its environmental implications - Dongxue Han; Yang Sun; Jinxin Cong; Chuanyu Gao; Guoping Wang (Environmental Science and Pollution Research, 2022)

Back-analysis of dynamic property of earth-rock dam considering parameter uncertainly - Hongyang Zhang; Ziyi Song; Yadong Sun; Zelin Ding; Xianqi Zhang; Pengju Han; Cong Ma (Arabian Journal of Geosciences, 2022)

Cytokine storm and targeted therapy in hemophagocytic lymphohistiocytosis - Han-qi Zhang; Si-Wei Yang; Yi-Cheng Fu; Ming-Cong Chen; Cheng-Hao Yang; Ming-Hua Yang; Xiao-Dan Liu; Qing-Nan He; Hua Jiang; Ming-Yi Zhao (Immunologic Research, 2022)

Construction of a core germplasm bank of upland cotton (Gossypium hirsutum L.) based on phenotype, genotype and favorable alleles - Peng Han; Xiaomin Tian; Ying Wang; Cong Huang; Yizan Ma; Xiaofeng Zhou; Yu Yu; Dawei Zhang; Haijiang Xu; Yang Cao; Bo Zhu; Zhenxiu Feng; et al. (Genetic Resources and Crop Evolution, 2022)

Streptococcus humanilactis sp.nov., isolated from healthy nursing mother's breast milk - Xiaoqing Guo; Fei Han; Lin Cong; Yu Li; Yue Wu; Chen Liu; Jingfang Yang; Risu Na; Wenjun Liu (Archives of Microbiology, 2022)

Paracandidimonas lactea sp. nov., a urea-utilizing bacterium isolated from landfill - Chu Zhang; Qian Pu; Jun-jie Ying; Ying Chen; Cheng-ze Li; Hang-tao Wu; Bin-jie Wang; Yu-han Zhang; Guo-hong Zeng; Ou Li; Xiu-fang Hu; Cong Sun (Archives of Microbiology, 2022)

Spray-Dried and Spray-Freeze-Dried Powder Formulations of an Anti-Interleukin-4Rα Antibody for Pulmonary Delivery - Harry W. Pan; Han Cong Seow; Jason C. K. Lo; Jinlin Guo; Lingqiao Zhu; Susan W. S. Leung; Chenghai Zhang; Jenny K. W. Lam (Pharmaceutical Research, 2022)

Inhibition of visfatin alleviates sepsis-induced intestinal damage by inhibiting Hippo signaling pathway - Zhong-Shen Kuang; Yu-Xin Leng; Ning Yang; Zheng-Qian Li; Ya-Nan Zong; Deng-Yang Han; Yue Li; Jin-Dan He; Xing-Ning Mi; Zhu-Kai Cong; Xi Zhu; Chang-Yi Wu; et al. (Inflammation Research, 2022)
Background The aim of this study is to investigate role of Visfatin, one of the pro-inflammatory adipokines, in sepsis-induced intestinal injury and to clarify the potential mechanism. Methods C57BL/6 mice underwent cecal ligation and puncture (CLP) surgery to establish sepsis model in vivo. Intestinal epithelial cells were stimulated with LPS to mimic sepsis-induced intestinal injury in vitro. FK866 (the inhibitor of Visfatin) with or without XMU-MP-1 (the inhibitor of Hippo signaling) was applied for treatment. The expression levels of Visfatin, NF-κB and Hippo signaling pathways-related proteins were detected by western blot or immunohistochemistry. The intestinal cell apoptosis and intestinal injury were investigated by TUNEL staining and H&E staining, respectively. ELISA was used to determine the production of inflammatory cytokines. Results The expression of Visfatin increased in CLP mice. FK866 reduced intestinal pathological injury, inflammatory cytokines production, and intestinal cell apoptosis in sepsis mice. Meanwhile, FK866 affected NF-κB and Hippo signaling pathways. Additionally, the effects of FK866 on inflammatory response, apoptosis, Hippo signaling and NF-κB signaling were partly abolished by XMU-MP-1, the inhibitor of Hippo signaling. In vitro experiments also revealed that FK866 exhibited a protective role against LPS-induced inflammatory response and apoptosis in intestinal cells, as well as regulating NF-κB and Hippo signaling, whereas addition of XMU-MP-1 weakened the protective effects of FK866. Conclusion In short, this study demonstrated that inhibition of Visfatin might alleviate sepsis-induced intestinal injury through Hippo signaling pathway, supporting a further research on Visfatin as a therapeutic target.

Driving Factors, Co-occurrence Networks, and Metabolic Profiles of Soil Bacterial Communities Within the Root Proximity of Amaranthus palmeri - Mei Zhang; Xueying Li; Cong Shi; Zhenlu Qiu; Jianhua Han; Kefan Wang; Pufan Zheng; Fuchen Shi (Journal of Soil Science and Plant Nutrition, 2022)

The regulation of shrimp metabolism by the white spot syndrome virus (WSSV) - Ramya Kumar; Jiun‐Yan Huang; Yen‐Siong Ng; Cong‐Yan Chen; Han‐Ching Wang (Reviews in Aquaculture, 2022)
For more than three decades, infectious diseases have been one of the major causes of economic losses in the global shrimp industry. One of the deadliest of the shrimp pathogens is white spot syndrome virus (WSSV), which causes mass mortality in farmed shrimp. Various aspects of WSSV pathogenicity have been studied, but in this review, we will focus only on one of them, namely metabolic reprogramming. WSSV’s modulation of host metabolism affects glycolysis, the tricarboxylic acid (TCA) cycle, glutaminolysis and lipid metabolism. Several signaling pathways are involved in this regulation, including JAK‐STAT, PI3K‐AKT‐mTOR, MAPK and Ras‐Raf‐MEK, with the PI3K‐Akt‐mTOR pathway in particular playing a critical role in activating the WSSV‐induced Warburg effect. Taken together, these changes benefit the virus by facilitating WSSV replication. In this review, we summarize current knowledge regarding the metabolism‐related aspects of WSSV pathogenesis, and discuss the mechanisms by which this virus reprograms its host's metabolic pathways. A deeper understanding of these pathways, key metabolic enzymes and signaling mechanisms is potentially important for the development of effective anti‐WSSV strategies.

Chemical characteristics, evolution, and quality of groundwater and processes controlling its fluoride concentration features: case study of a typical high-fluoride areas in the Southwestern Shandong Plain, China - Cong Han; Jiutan Liu; Zongjun Gao; Yuan Xu; Yuqi Zhang; Zheng Han; Zhenhua Zhao; Zhenjiang Luo (Environmental Science and Pollution Research, 2022)

Assessment of the hydrochemistry, water quality, and human health risk of groundwater in the northwest of Nansi Lake Catchment, north China - Zongjun Gao; Cong Han; Shuyu Yuan; Jiutan Liu; Yuming Peng; Changsuo Li (Environmental Geochemistry and Health, 2022)

The adaptation mechanism based on an integrated vulnerability assessment of potato production to climate change in Inner Mongolia, China - Na Huang; Jialin Wang; Yu Song; Yuying Pan; Guolin Han; Ziyuan Zhang; Shangqian Ma; Guofeng Sun; Cong Liu; Zhihua Pan (Mitigation and Adaptation Strategies for Global Change, 2022)

Petrogenesis of the Late Triassic Mengsong strongly peraluminous granites in the southeastern Tibetan Plateau: highly fractionated from crystal mush - Feng Cong; Fu-Yuan Wu; Wen-Chang Li; De-Feng He; Zai-Bo Sun; Xiao-Ming Huang; Zhi-Zhong Hu; Han Zhao (International Geology Review, 2022)

Influence Mechanism of Geomorphological Evolution in a Tidal Lagoon with Rising Sea Level - Cuiping Kuang; Jiadong Fan; Zhichao Dong; Qingping Zou; Xin Cong; Xuejian Han (Journal of Marine Science and Engineering, 2022)
A tidal lagoon system has multiple environmental, societal, and economic implications. To investigate the mechanism of influence of the geomorphological evolution of a tidal lagoon, the effect of critical erosion shear stress, critical deposition shear stress, sediment settling velocity, and initial bed elevation were assessed by applying the MIKE hydro- and morpho-dynamic model to a typical tidal lagoon, Qilihai Lagoon. According to the simulation results, without sediment supply, an increase of critical erosion, deposition shear stress, or sediment settling velocity gives rise to tidal networks with a stable terrain. Such an equilibrium state can be defined as when the change of net erosion has little variation, which can be achieved due to counter actions between the erosion and deposition effect. Moreover, the influence of the initial bed elevation depends on the lowest tidal level. When the initial bed elevation is below the lowest tidal level, the tidal networks tend to be fully developed. A Spearman correlation analysis indicated that the geomorphological evolution is more sensitive to critical erosion or deposition shear stress than sediment settling velocity and initial bed elevation. Exponential sea level rise contributes to more intensive erosion than the linear or the parabolic sea level rise in the long-term evolution of a tidal lagoon.

Halomonas populi sp. nov. isolated from Populus euphratica - Lin Xu; Jun-Jie Ying; Yuan-Chun Fang; Ran Zhang; Jia Hua; Min Wu; Bing-Nan Han; Cong Sun (Archives of Microbiology, 2022)

Polymorphism in the Ras and β-Glucosidase Genes and Their Association with Growth Traits in the Pacific Oyster Crassostrea gigas - Ziqiang Han; Rihao Cong; Qi Li (Journal of Ocean University of China, 2021)

Loganin ameliorates depression-like behaviors of mice via modulation of serotoninergic system - Chen-Hao Pan; Cong-Yuan Xia; Yu Yan; Yan Han; Rui Shi; Jun He; Ze-Xing Wang; Yu-Ming Wang; Wei-Ku Zhang; Jie-Kun Xu (Psychopharmacology, 2021)

Lipin1 Alleviates Autophagy Disorder in Sciatic Nerve and Improves Diabetic Peripheral Neuropathy - Meijian Wang; Min Xie; Shuyan Yu; Pan Shang; Cong Zhang; Xiaolin Han; Cuiqin Fan; Li Chen; Xianghua Zhuang; Shihong Chen (Molecular Neurobiology, 2021)

Marinomonas vulgaris sp. nov., a marine bacterium isolated from seawater in a coastal intertidal zone of Zhoushan island - Jun-Jie Ying; Yuan-Chun Fang; Yong-Lian Ye; Zhi-Cheng Wu; Lin Xu; Bing-Nan Han; Cong Sun (Archives of Microbiology, 2021)

Pinocembrin-7-Methylether Protects SH-SY5Y Cells Against 6-Hydroxydopamine-Induced Neurotoxicity via Modulating Nrf2 Induction Through AKT and ERK Pathways - Zhi-Cong Zou; Ji-Jun Fu; Yuan-Ye Dang; Qian Zhang; Xiu-Fen Wang; Han-Bin Chen; Xue-Jing Jia; Simon Ming-Yuen Lee; Chu-Wen Li (Neurotoxicity Research, 2021)

Hydrogeochemical and isotopic characteristics of spring water in the Yarlung Zangbo River Basin, Qinghai-Tibet Plateau, Southwest China - Ying-zhi Li; Zong-jun Gao; Jiu-tan Liu; Min Wang; Cong Han (Journal of Mountain Science, 2021)

Pangasius Catfish Feeding with Flammulina velutipes Extract Decreases the Disease Ratio, Prevents Lipid Oxidation, Structure Damage and Color Changes during Cool Preservation - Nguyen Cong Ha; Le Thi Bich Hiep; Le Toan; Khuu Thi Ngoc Han; Le Thi Hong Nho; Huynh Cam Nhu; Pham Thi Ngoc Nhu; Nguyen Thi Ngoc Tuyet; Nguyen Thi Ngoc; Ibitoye Joshua Oladapo (Journal of Aquatic Food Product Technology, 2021)

Mutation analysis of 28 autosomal short tandem repeats in the Chinese Han population - Yujie Huang; Cong Liu; Chao Xiao; Xiaoying Chen; Xueli Han; Shaohua Yi; Daixin Huang (Molecular Biology Reports, 2021)

Breast milk contains probiotics with anti‐infantile diarrhoea effects that may protect infants as they change to solid foods - Haiyue Niu; Xiaohong Zhou; Xuguang Zhang; Tongjie Liu; Yifan Wu; Linzheng Lyu; Cong Liang; Shiwei Chen; Pimin Gong; Jiliang Zhang; Xue Han; Shilong Jiang; et al. (Environmental Microbiology, 2021)
Summary Infants often experience complementary food‐induced diarrhoea (CFID), which occurs when infants switch from breast milk to solid foods. The relative abundances of Prevotella and Rothia were higher in stools of infants with CFID, while the relative abundances of Enterococcus and Escherichia were higher in healthy infants. The abundance of Lactobacillus spp . normally found in breast milk fed to infants with CFID was significantly reduced, and Enterococcus spp. were less abundant when diarrhoea occurred. Furthermore, Lactobacillus and Enterococcus were present as shared bacteria in both mother and infant, and they were considered potential anti‐CFID probiotics as their relative abundances in breast milk were negatively correlated to infant CFID. Kyoto encyclopedia of genes and genomes (KEGG) functional analysis showed that the function of amino acid metabolism differed between infants with CFID and healthy infants. Therefore, CFID might be related to the decomposition of proteins in food supplements. The screening revealed seven hydrolytic casein and five hydrolytic casein and rice protein isolates from 320 suspected Lactobacillus and Enterococcus isolates. The animal experiments demonstrated that a mixture of five isolates effectively hydrolysed the casein and rice protein and prevented diarrhoea in young rats. Thus, the occurrence of CFID was found to be closely related to the intestinal and breast milk microbiota, and bacteria that could assist in the digestion of cereal proteins were involved in CFID.

Pore pressure and spalling in fire-exposed high-strength self-consolidating concrete reinforced with hybrid fibres - Cong Zhang; Jincheng Liu; Shicheng Han; Yuan Hua (European Journal of Environmental and Civil Engineering, 2021)

Determination of Landscape Ecological Network of Wetlands in the Yellow River Delta - Pifu Cong; Kexin Chen; Limei Qu; Jianbo Han; Zhengxian Yang (Wetlands, 2020)

Two novel recombinant avian leukosis virus isolates from Luxi gamecock chickens - Peikun Wang; Jianrui Niu; Cong Xue; Zhaoqing Han; Amro Abdelazez; Zhang Xinglin (Archives of Virology, 2020)

Effects of ferric and manganese precursors on catalytic activity of Fe-Mn/TiO2 catalysts for selective reduction of NO with ammonia at low temperature - Huan Du; Zhitao Han; Qimeng Wang; Yu Gao; Cong Gao; Jingming Dong; Xinxiang Pan (Environmental Science and Pollution Research, 2020)

Accelerated remediation of organochlorine pesticide-contaminated soils with phyto-Fenton approach: a field study - Trinh Dinh Tran; Nhung Thi Dao; Rei Sasaki; Minh Binh Tu; Giang Huong Minh Dang; Han Gia Nguyen; Hieu Minh Dang; Cong Huu Vo; Yoshihiko Inigaki; Noi Van Nguyen; Yutaka Sakakibara (Environmental Geochemistry and Health, 2020)

Exploring slope spatial heterogeneity by nitrogen transfer and arbuscular mycorrhizal community - Yanyan Yu; Lu Zhao; Min Cui; Yutong Xiao; Cong Wang; Yuan Miao; Zhijie Chen; Yanhong Cao; Junqiang Zheng; Shijie Han (Journal of Soils and Sediments, 2020)

Molecular characterization of an emerging reassortant mammalian orthoreovirus in China - Dandan Ye; Zhaoyang Ji; Hongyan Shi; Jianfei Chen; Da Shi; Liyan Cao; Jianbo Liu; Mingwei Li; Hui Dong; Zhaoyang Jing; Xiaobo Wang; Qiuge Liu; et al. (Archives of Virology, 2020)

Dominant complementary interaction between OsC1 and two tightly linked genes, Rb1 and Rb2, controls the purple leaf sheath in rice - Wei Hu; Tianhao Zhou; Zhongmin Han; Cong Tan; Yongzhong Xing (Theoretical and Applied Genetics, 2020)

Removal of boron and silicon by a modified resin and their competitive adsorption mechanisms - Shuqin Bai; Jue Han; Cong Du; Jiaxin Li; Wei Ding (Environmental Science and Pollution Research, 2020)

Prognostic Relationship Between Peripheral Red Cell Distribution Width and Acute Cerebral Infarction in Patients with rtPA Thrombolysis - Lin Cong; Han Gao; Weining Ma (Neurotoxicity Research, 2020)

Membrane proteomic analysis reveals the intestinal development is deteriorated by intrauterine growth restriction in piglets - Shimeng Huang; Cong Liu; Na Li; Zhenhua Wu; Tiantian Li; Dandan Han; Zhen Li; Jiangchao Zhao; Junjun Wang (Functional & Integrative Genomics, 2020)

Unsupervised classification for PolSAR images based on multi-level feature extraction - Ping Han; Binbin Han; Xiaoguang Lu; Runmin Cong; Dandan Sun (International Journal of Remote Sensing, 2020)

History metal (Pb, Zn, and Cu) deposition and Pb isotope variability in multiple peatland sites in the northern Great Hinggan Mountains, Northeast China - Jinxin Cong; Chuanyu Gao; Dongxue Han; Hanxiang Liu; Guoping Wang (Environmental Science and Pollution Research, 2019)

Dynamic Changes in the Wetland Landscape Pattern of the Yellow River Delta from 1976 to 2016 Based on Satellite Data - Pifu Cong; Kexin Chen; Limei Qu; Jianbo Han (Chinese Geographical Science, 2019)

Genetic analysis of cob resistance to F. verticillioides: another step towards the protection of maize from ear rot - Cong Mu; Jingyang Gao; Zijian Zhou; Zhao Wang; Xiaodong Sun; Xuecai Zhang; Huafang Dong; Yanan Han; Xiaopeng Li; Yabin Wu; Yunxia Song; Peipei Ma; et al. (Theoretical and Applied Genetics, 2019)

Manganese induces neuroinflammation via NF-κB/ROS NLRP3 pathway in rat brain striatum and HAPI cells - Xinyuan Zhao; Lifeng Yin; Yifan Wu; Muxi Han; Yin Zhuang; Yewen Cong; Yiming Liu; Gang Chen; Junkang Jiang (Molecular & Cellular Toxicology, 2019)

Chemical constituents from the fruits of Psoralea corylifolia and their protective effects on ionising radiation injury - Jie Du; Chun-Hua Wang; Jing Yang; Xin He; Xiao-Liang Han; Cong-Cong Li; Xin Chai; Yue-Fei Wang; Yan Zhu; Zheng Li (Natural Product Research, 2019)

Confluentibacter flavum sp. nov., Isolated from the Saline Lake - Yu. Li; Xin-Jun Hou; Xia Shen; Shuai-Bo Han; Zhao Ju; Zhe Zhao; Xiao-Yun Yu; Min Wu; Cong Sun (Current Microbiology, 2018)

Spatial Properties of Mismatch Negativity in Patients with Disorders of Consciousness - Xiaoyu Wang; Rao Fu; Xiaoyu Xia; Xueling Chen; Han Wu; Nicole Landi; Ken Pugh; Jianghong He; Fengyu Cong (Neuroscience Bulletin, 2018)

Analysis of the function of KIF3A and KIF3B in the spermatogenesis in Boleophthalmus pectinirostris - Yong-Qiang Zhao; Dan-Li Mu; Di Wang; Ying-Li Han; Cong-Cong Hou; Jun-Quan Zhu (Fish Physiology and Biochemistry, 2018)

Cotton (Gossypium hirsutum) JAZ3 and SLR1 function in jasmonate and gibberellin mediated epidermal cell differentiation and elongation - Xiao-Cong Xia; Qian-Qian Hu; Wen Li; Yun Chen; Li-Hong Han; Miao Tao; Wen-Ying Wu; Xue-Bao Li; Geng-Qing Huang (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Cell shape can be uncoupled from formononetin induction in a novel cell line from Callerya speciosa - Fei Qiao; Xue-fei Jiang; Han-qing Cong; Hua-peng Sun; Li Li; Peter Nick (Plant Cell Reports, 2018)

Polyphasic taxonomic characterisation of a novel strain as Pararhizobium haloflavum sp. nov., isolated from soil samples near a sewage treatment tank - Xia Shen; Yu Li; Zhe Zhao; Yi-Fan Han; Wen-Wu Zhang; Xiao-Yun Yu; Chong-Ya Zhang; Cong Sun; Min Wu (Antonie van Leeuwenhoek, 2018)

Historical pyrogenic sources of black carbon during the last 150 years in the Great Hinggan Mountains, Northeast China - Jiabao He; Chuanyu Gao; Jinxin Cong; Jingjing Zhong; Dongxue Han; Guoping Wang (Journal of Soils and Sediments, 2018)

Complete nucleotide sequence of jasmine virus H, a new member of the family Tombusviridae - Tao Zhuo; Li-Juan Zhu; Cheng-Cong Lu; Chao-Yang Jiang; Zi-Yin Chen; Guangzhi Zhang; Zong-Hua Wang; Juan Jovel; Yan-Hong Han (Archives of Virology, 2018)

Large soil organic carbon increase due to improved agronomic management in the North China Plain from 1980s to 2010s - Daorui Han; Martin Wiesmeier; Richard T. Conant; Anna Kühnel; Zhigang Sun; Ingrid Kögel‐Knabner; Ruixing Hou; Peifei Cong; Rubiao Liang; Zhu Ouyang (Global Change Biology, 2018)
Agricultural soils are widely recognized to be capable of carbon sequestration that contributes to mitigating CO 2 emissions. To better understand soil organic carbon ( SOC ) stock dynamics and its driving and controlling factors corresponding with a period of rapid agronomic evolution from the 1980s to the 2010s in the North China Plain ( NCP ), we collected data from two region‐wide soil sampling campaigns (in the 1980s and 2010s) and conducted an analysis of the controlling factors using the random forest model. Between the 1980s and 2010s, environmental (i.e. soil salinity/fertility) and societal (i.e. policy/techniques) factors both contributed to adoption of new management practices (i.e. chemical fertilizer application/mechanization). Results of our work indicate that SOC stocks in the NCP croplands increased significantly, which also closely related to soil total nitrogen changes. Samples collected near the surface (0–20 cm) and deeper (20–40 cm) both increased by an average of 9.4 and 5.1 Mg C ha −1 , respectively, which are equivalent to increases of 73% and 56% compared with initial SOC stocks in the 1980s. The annual carbon sequestration amount in surface soils reached 10.9 Tg C year −1 , which contributed an estimated 43% of total carbon sequestration in all of China's cropland on just 27% of its area. Successful desalinization and the subsequent increases in carbon (C) inputs, induced by agricultural projects and policies intended to support crop production (i.e. reconstruction of low yield farmland, and agricultural subsidies), combined with improved cultivation practices (i.e. fertilization and straw return) since the early 1980s were the main drivers for the SOC stock increase. This study suggests that rehabilitation of NCP soils to reduce salinity and increase crop yields have also served as a pathway for substantial soil C sequestration.

3,5-Bis(2-fluorobenzylidene)-4-piperidone induce reactive oxygen species-mediated apoptosis in A549 cells - Guo-Yun Liu; Cong-Cong Jia; Pu-Ren Han; Jie Yang (Medicinal Chemistry Research, 2018)

Simulated nitrogen deposition significantly suppresses the decomposition of forest litter in a natural evergreen broad-leaved forest in the Rainy Area of Western China - Shi-xing Zhou; Cong-de Huang; Bo-han Han; Yong-xiang Xiao; Jian-dong Tang; Yuan-bin Xiang; Chao Luo (Plant and Soil, 2017)

Characterization of mitochondrial prohibitin from Boleophthalmus pectinirostris and evaluation of its possible role in spermatogenesis - Di Wang; Yong-Qiang Zhao; Ying-Li Han; Cong-Cong Hou; Jun-Quan Zhu (Fish Physiology and Biochemistry, 2017)

Seasonal variations of organic carbon and nitrogen in the upper basins of Yangtze and Yellow Rivers - Xiang-ying Li; Yong-jian Ding; Tian-ding Han; Jian-zhong Xu; Shi-chang Kang; Qing-bai Wu; Mika Sillanpää; Zhong-bo Yu; Cong-rong Yu (Journal of Mountain Science, 2017)

RETRACTED ARTICLE: Neural auditory intensity discrimination during naturalistic listening: a brain decoding study - Xintao Hu; Lei Guo; Junwei Han; Christine Cong Guo (Brain Structure and Function, 2017)

Novel hemostatic agents based on gelatin-microbial transglutaminase mix - Fang Lv; Xiaonan Cong; Wenshu Tang; Yiming Han; Yu Tang; Yongrui Liu; Liqiang Su; Mingyao Liu; Mingfei Jin; Zhengfang Yi (Science China Life Sciences, 2017)

Therapeutic value of nerve growth factor in promoting neural stem cell survival and differentiation and protecting against neuronal hearing loss - Zhao Han; Cong-Pin Wang; Ning Cong; Yu-Yan Gu; Rui Ma; Fang-Lu Chi (Molecular and Cellular Biochemistry, 2017)

QTLs for heading date and plant height under multiple environments in rice - Zhongmin Han; Wei Hu; Cong Tan; Yongzhong Xing (Genetica, 2017)

Structuraland antigenic analysis of a new Rhoptry Pseudokinase Gene (ROP54) in Toxoplasma gondii - Jian Zhou; Gang Lu; Lin Wang; Aihua H. Zhou; Yali L. Han; Jingjing J. Guo; Pengxia X. Song; Huaiyu Y. Zhou; Hua Cong; Ming Hou; Shenyi Y. He (Acta Parasitologica, 2017)
is defined as an obligate intracellular apicomplexan parasite and influences approximatelyone-third of the human all over the world. ROP54 protein is expressed in the rhoptry of

Mitochondrial aldehyde dehydrogenase 2 deficiency aggravates energy metabolism disturbance and diastolic dysfunction in diabetic mice - Cong Wang; Fan Fan; Quan Cao; Cheng Shen; Hong Zhu; Peng Wang; Xiaona Zhao; Xiaolei Sun; Zhen Dong; Xin Ma; Xiangwei liu; Shasha Han; et al. (Journal of Molecular Medicine, 2016)

Streptomyces xinjiangensis sp. nov., an actinomycete isolated from Lop Nur region - Cong Cheng; Yu-Qian Li; Mipeshwaree Devi Asem; Chun-Yan Lu; Xiao-Han Shi; Xiao Chu; Wan-Qin Zhang; Deng- Di An; Wen-Jun Li (Archives of Microbiology, 2016)

Effect of cadmium exposure on antioxidant enzyme catalase in different tissues of Acrossocheilus fasciatus - Yong-Qiang Zhao; Guo-Di Liu; Cong-Cong Hou; Ying-Li Han; Jun-Quan Zhu (Molecular & Cellular Toxicology, 2016)

From folding to transpressional faulting: the Cenozoic Fusha structural belt in front of the Western Kunlun Orogen, northwestern Tibetan Plateau - Cong Wang; Xiao-Gan Cheng; Han-Lin Chen; Kang Li; Xiao-Gen Fan; Chun-Yang Wang (International Journal of Earth Sciences, 2016)

Molecular identification of ‘Candidatus phytoplasma asteris’ related strain (16SrΙ-B) associated with Broussonetia papyrifera in Nanjing, China - Cong-Jin Mei; Qing-Can Wang; Ju-Can Gui; Yan-Ling Ji; Han-Shou Yu (European Journal of Plant Pathology, 2016)

Morphology, sex steroid level and gene expression analysis in gonadal sex reversal of triploid female (XXX) rainbow trout (Oncorhynchus mykiss) - Gefeng Xu; Tianqing Huang; Xian Jin; Cunhe Cui; Depeng Li; Cong Sun; Ying Han; Zhenbo Mu (Fish Physiology and Biochemistry, 2016)

The prevalence of helminth parasites in Pelophylax nigromaculatus (Anura: Ranidae) from Shanghai, China - Qifei Men; Hongyu Han; Qiping Zhao; Weili Xia; Hui Dong; Shunhai Zhu; Ziwen Wang; Cong Li; Xuelong Zhu; Bing Huang (Acta Parasitologica, 2016)
Parasites are ubiquitous members of biotic communities. To investigate the infective status of helminth parasites in

A Mouse Model of Hypospadias Induced by Estradiol Benzoate - Hou-Guang He; Cong-hui Han; Wei Zhang (Cell Biochemistry and Biophysics, 2015)

Multi-scale crown closure retrieval for moso bamboo forest using multi-source remotely sensed imagery based on geometric-optical and Erf-BP neural network models - Cong Wang; Huaqiang Du; Xiaojun Xu; Ning Han; Guomo Zhou; Shaobo Sun; Guolong Gao (International Journal of Remote Sensing, 2015)

Optimization Studies on Prokaryotic Cell Expression of the Human Tumor Necrosis Factor-Related Apoptosis-Inducing Ligand (TRAIL) - Lin Hao; Zhi-Guo Zhang; Zheng-Duo Shi; Kun Pang; Jun-Jie Zhang; Yang Dong; Cong-Hui Han (Cell Biochemistry and Biophysics, 2015)

Detection and identification of ‘Candidatus Phytoplasma ziziphi’ associated with violet orychophragmus yellow dwarf disease in China - Qing-Can Wang; Cong-Jin Mei; Ju-Can Gui; Yan-Ling Ji; Han-Shou Yu (Journal of General Plant Pathology, 2015)

Saccharothrix lopnurensis sp. nov., a filamentous actinomycete isolated from sediment of Lop Nur - Yu-Qian Li; Lan Liu; Cong Cheng; Xiao-Han Shi; Chun-Yan Lu; Zhou-Yan Dong; Nimaichand Salam; Deng-Di An; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Diaphorobacter ruginosibacter sp. nov., isolated from soybean root nodule, and emended description of the genus Diaphorobacter - Xiu Li Wei; Meng Sha Han; Cong Cong Xia; Shu Lan Ding; Lin Xu; Yan Bing Lin; Li Wang; Ge Hong Wei (Archives of Microbiology, 2015)

The expression level of anthocyanidin synthase determines the anthocyanin content of crabapple (Malus sp.) petals - Jie Zhang; Zhen-yun Han; Ji Tian; Xi Zhang; Ting-ting Song; Yun-cong Yao (Acta Physiologiae Plantarum, 2015)

Tobacco rattle virus mediated gene silencing in strawberry plants - Ji Tian; Li Cheng; Zhen-yun Han; Yun-cong Yao (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Protective Effects of Wusen Erlian Granules in Experimental Model of Viral Myocarditis - Yong Cao; Lin Hao; Cong-hui Han; Pei-ying Zhang (Cell Biochemistry and Biophysics, 2015)

In Vitro Cardioprotective Effect of Wusen Erlian Granules Through the Inhibition of Coxsackievirus B3 Replication - Yong Cao; Lin Hao; Cong-hui Han; Pei-ying Zhang (Cell Biochemistry and Biophysics, 2015)

The geometric factor of high energy protons detector on FY-3 satellite - ShenYi Zhang; XianGuo Zhang; ChuiQin Wang; GuoHong Shen; Tao Jin; BinQuan Zhang; YueQiang Sun; GuangWu Zhu; JinBao Liang; XiaoXin Zhang; JiaWei Li; Cong Huang; et al. (Science China Earth Sciences, 2014)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

Re-Transurethral Resection Treatment for Non-invasive Bladder Tumor - Cong-hui Han; Zhenduo Shi; Xujun Xuan; Bo Chen; Bingzheng Dong; Lin Hao; Xiangzheng Qiu; Xiangju Zhou; Tian-lin Wu; Dong Liu (Cell Biochemistry and Biophysics, 2014)

Ecological risks and potential sources of heavy metals in agricultural soils from Huanghuai Plain, China - Lingli Zhou; Bing Yang; Nandong Xue; Fasheng Li; Hans Martin Seip; Xin Cong; Yunzhong Yan; Bo Liu; Baolu Han; Huiying Li (Environmental Science and Pollution Research, 2014)

Natural antisense transcripts of UL123 packaged in human cytomegalovirus virions - Cui-Qing Yang; Ling-Feng Miao; Xing Pan; Cong-Cong Wu; Simon Rayner; Edward S. Mocarski; Han-Qing Ye; Min-Hua Luo (Archives of Virology, 2014)

Effect of combined treatment with recombinant interleukin-2 and allicin on pancreatic cancer - Cong-Jun Wang; Chao Wang; Jiang Han; Yong-Kun Wang; Lin Tang; Dong-Wei Shen; Yi Zhao; Rong-Hua Xu; Hui Zhang (Molecular Biology Reports, 2013)

The Transurethral Seminal Vesiculoscopy in the Diagnosis and Treatment of the Seminal Vesicle Disease - Cong-hui Han; Qing Liang; Bing-zheng Dong; Lin Hao; Tao Fan; Jun-jie Zhang; Wen-da Zhang; Bo Chen; Xiang-zheng Qiu; Xiang-ju Zhou; Chang-song Pei (Cell Biochemistry and Biophysics, 2013)

Functional analysis of BT4 of Arabidopsis thaliana in resistance against Botrytis cinerea - Cong-Cong Hao; Jiao Jia; Zhan Chen; Ji-Hong Xing; Qiao-Yun Weng; Feng-Ru Wang; Jin-Gao Dong; Jian-Min Han (Australasian Plant Pathology, 2013)

Developmental changes in lysophospholipid receptor expression in rodent heart from near-term fetus to adult - Fang Wang; Jianfeng Hou; Bianmei Han; Yu Nie; Xiangfeng Cong; Shengshou Hu; Xi Chen (Molecular Biology Reports, 2012)

Physiological significance of P2X receptor-mediated vasoconstriction in five different types of arteries in rats - Lu Li; Zhen-Hua Jia; Chao Chen; Cong Wei; Jian-Ke Han; Yi-Ling Wu; Lei-Ming Ren (Purinergic Signalling, 2011)

Influence of temperature and salinity on germination of eelgrass (Zostera marina L.) seeds - Jinhua Pan; Xin Jiang; Xiaojie Li; Yizhou Cong; Zhuangzhi Zhang; Zhiling Li; Weili Zhou; Houwei Han; Shiju Luo; Guanpin Yang (Journal of Ocean University of China, 2011)

Isolation of protoplasts and ion channel recording of plasma membrane patches and whole-cell recordings of the marine alga, Ulva pertusa (Chlorophyta) - Shenghao Liu; Xiaohang Huang; Chenlin Liu; Bailin Cong; Guang Han (Journal of Applied Phycology, 2008)

Cloning of a novel human NHEDC1 (Na+/H+ exchanger like domain containing 1) gene expressed specifically in testis - Guangming Ye; Cong Chen; Dingding Han; Xiabin Xiong; Yahui Kong; Bo Wan; Long Yu (Molecular Biology Reports, 2006)

Efficient shoot regeneration andAgrobacterium-mediated transformation ofBrassica juncea - Zhang Yuxiu; Xu Jin; Han Lu; Wei Wei; Guan Ziqiu; Cong Lin; Chai Tuanyao (Plant Molecular Biology Reporter, 2006)

Characterization of soybean genomic features by analysis of its expressed sequence tags - Ai-Guo Tian; Jun Wang; Peng Cui; Yu-Jun Han; Hao Xu; Li-Juan Cong; Xian-Gang Huang; Xiao-Ling Wang; Yong-Zhi Jiao; Bang-Jun Wang; Yong-Jun Wang; Jin-Song Zhang; et al. (Theoretical and Applied Genetics, 2004)

Growth characteristics and eicosapentaenoic acid production by Nannochloropsis sp. in mixotrophic conditions - Fang Xu; Han-hua Hu; Wei Cong; Zhao-ling Cai; Fan Ouyang (Biotechnology Letters, 2004)